Polyamide composition for improving damping properties

CN122935577APending Publication Date: 2026-10-16BASF SE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580017948.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-02-29
Filing Date
2025-02-27
Publication Date
2026-10-16

Smart Images

  • Figure CN122935577A_ABST
    Figure CN122935577A_ABST
Patent Text Reader

Abstract

Provided are polyamide compositions having an amorphous / semi-crystalline ratio comprising one or more amorphous polyamides and one or more semi-crystalline polyamides, such as PA66, PA6, PA66 / 6, and PA9T. These compositions are particularly useful as vibration isolators that are more effective at high temperature noise and sound vibration roughness damping than conventional polyamide compositions. Also provided are methods for making the provided compositions, connected parts and articles comprising the provided compositions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polymer compositions comprising polyamide compositions, particularly polyamide compositions exhibiting improved damping properties over a wide temperature range, making these compositions suitable for vibration damping and noise suppression in transport vehicles. The compositions of this invention are particularly suitable for automotive vibration isolators. Background Technology

[0002] There is a need for polymer compositions, particularly polyamide compositions, that exhibit high damping properties over a wide temperature range. Such polyamide compositions can be used for vibration damping and noise suppression in transport vehicles.

[0003] Noise and vibration problems are typically managed in two ways: strengthening the structural geometry to make it more resistant to vibration, and strengthening the structural damping to reduce vibration.

[0004] US Publication No. 2021 / 0355322 A1 discloses a polyamide formulation for noise vibration and acoustic roughness. International PCT Application No. WO2012 / 092093 discloses a noise damping composition. US Publication No. US2008 / 0026246 A1 discloses a vibration damping material of polyamide and mercaptobenzimidazole.

[0005] The vibration damping characteristics of polymer materials depend on viscoelasticity. Typically, vibration damping is expressed as the loss factor (the peak value of tandelta (δ), which is a measure of the conversion of external vibrational energy into heat energy).

[0006] Dynamic mechanical analysis (DMA) provides a method for measuring the polymer loss factor, or tan delta (δ), as the ratio of dissipated energy to stored energy. Generally, in polyamide compositions, the loss factor is below 0.1 in the temperature range of 20°C to 180°C.

[0007] To improve the damping properties of polyamide compositions and provide effective noise and vibration absorption at higher temperatures while maintaining the desired mechanical strength characteristics, it is desirable to increase their loss factor. Summary of the Invention

[0008] The present invention provides a composition comprising: one or more amorphous polyamides (A); one or more semi-crystalline polyamides (C); wherein the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C; wherein the A / C ratio is from 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02.

[0009] The present invention also provides a composition comprising: >0 wt% to 50 wt% of a semi-crystalline PA66 / 6 (co)polyamide; 0 wt% to 55 wt% of a material selected from a list of compositions of a second semi-crystalline polyamide and an amorphous polyamide; wherein the composition has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C; and wherein the A / C ratio is 0.40 to 4.00, and does not include the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02;

[0010] The present invention further provides a composition comprising: T g High T for 100℃ to 200℃ g Polymers and T g Low T from 0℃ to 160℃ g The polymer, wherein the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C, and wherein the A / C ratio is from 0.40 to 4.00, and excludes the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

[0011] The present invention also provides a connecting part comprising: a part body for contacting a first component; and a part tab for contacting a second component to connect the first component and the second component, wherein at least one of the part body and the part tab comprises a composition comprising: one or more amorphous polyamides; and one or more semi-crystalline polyamides; one or more semi-crystalline polyamides; and an A / C ratio of 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02; wherein the part has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C.

[0012] The present invention also provides a connecting component, the component comprising: a component body for contacting a first component; and a component tab for contacting a second component to connect the first component and the second component, wherein at least one of the component body and the component tab comprises a composition comprising: 0 wt% to 55 wt% of semi-crystalline PA66 polyamide; 0 wt% to 60 wt% of semi-crystalline PA6 polyamide; 0 wt% to 20 wt% of semi-crystalline PA66 / 6 polyamide; 0 wt% to 35 wt% of semi-crystalline PA9T polyamide; and 15 wt% to 50 wt% of... The composition comprises: 15% to 60% glass fiber; 0.1% to 2% stearate; 0.01% to 2% stabilizer; 0% to 2% colorant; and wherein the part has a maximum tan(δ) greater than 0.05 in the temperature range of 20°C to 180°C, wherein the A / C ratio is 0.40 to 4.00, and excludes the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

[0013] The present invention provides a method for connecting a first component to a second component, the method comprising: providing a connecting component including a component body and a component tab; contacting the component body with the first component; and contacting the component tab with the second component to connect the first component and the second component, wherein the component has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C, wherein the A / C ratio is from 0.40 to 4.00, and excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

[0014] The present invention further provides a composition comprising one or more amorphous polyamides (A) and one or more semi-crystalline polyamides (C). The composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 at a temperature range of 20°C to 180°C or greater than 40°C, for example, greater than 50°C or greater than 60°C (ranging from 65°C to 130°C, for example, 65.4°C to 113.9°C, including 86.9°C to 95.7°C), and wherein the A / C ratio is greater than 0.40. In one aspect of the invention, the A / C ratio is from 0.40 to 4.00. In another aspect, the composition has a moisture content of less than 0.2% by weight. Attached Figure Description

[0015] Figure 1Dynamic mechanical analysis (DMA) curves of the tan Delta (δ) properties of some embodiments of the polyamide compositions described herein are shown.

[0016] Figure 2 The DMA tan Delta curves of embodiments of the polyamide compositions described herein are shown.

[0017] Figure 3 The DMA tan Delta curves of another embodiment of the polyamide composition described herein are shown. Detailed Implementation

[0018] The present invention relates generally to polyamide compositions that, when used, for example, as damping materials, provide advantageous improvements in vibration and noise isolation characteristics at elevated operating temperatures.

[0019] For example, although not yet realized, it would be beneficial for polyamide compositions to possess sufficient damping capacity (e.g., as measured by the viscoelastic loss factor tan(δ)) to effectively isolate vibrations under operating conditions that may exist in certain automotive applications and may include temperatures exceeding 60°C, 65°C, 75°C, 85°C, 90°C, and even 95°C. One measure of the damping performance of the provided compositions is the temperature at which the viscoelastic loss factor (tan(δ)) exhibits its maximum value. Generally, the higher the temperature at which this maximum value is reached, the better the composition's effect on damping and isolating vibrations and noise at higher temperatures. It is also beneficial for polyamide compositions to exhibit good strength properties at these elevated ambient temperatures (e.g., high tensile strength, high tensile modulus, high fracture stress, high fracture strain, high elongation at break, improved impact resistance, and improved fatigue resistance).

[0020] Polyamides are hygroscopic and tend to absorb moisture, and the performance properties of polyamide compositions can vary based on the moisture content of the composition. Because some applications (e.g., automotive parts) typically operate under high temperature and / or high humidity conditions, where humidity may vary by geographic jurisdiction, low-moisture compositions have been found to be particularly desirable. In particular, compositional moisture should be considered when using (lightweight) hygroscopic polymers (e.g., nylon). Therefore, it has been found that performance measured at low moisture contents, such as tan(δ) performance at low moisture contents (e.g., less than or equal to 0.2 wt%, 0.1 wt%, or 0.05 wt%), is a particularly closely relevant metric because it provides a baseline metric with little or no external environmental influence. When utilizing higher moisture contents and weighting performance measurements, more uncertainty may exist regarding performance and its measurement. Importantly, measurements / performance at low moisture contents may not correspond to measurements / performance at high moisture contents. This is especially true for hygroscopic polymers. Advantageously, the polyamide compositions disclosed herein generally exhibit a favorable combination of performance properties, especially when measured at low water content.

[0021] However, achieving these performance characteristics is difficult for conventional polyamide compositions. One reason is that conventional compositions (with low moisture content or otherwise) exhibit their peak tan(δ) at or below 60°C (e.g., below 40°C), indicating that the composition's maximum damping capacity is only observed at lower temperatures. Furthermore, modifications typically used to enhance polyamide compositions most often have the effect of deteriorating the thermal and damping properties of these materials, thereby further reducing the temperature at which they exhibit peak tan(δ).

[0022] The inventors have discovered that specific combinations of the polyamides disclosed herein (optionally added in specific types, amounts, and ratios) can be used to form compositions with improved, higher maximum tan(δ) temperatures. In particular, these results have been found in compositions combining a semi-crystalline polyamide (C) (or C1) with any of the following: 1) an amorphous polyamide (A), such as PA6I / 6T polyamide; and / or 2) another semi-crystalline polyamide (C2), such as PA66 / 6, PA66, PA6, PA9T, or PA66 / 6C polyamide (where C or C1 may differ from C2). It is noteworthy that the importance of amorphous polyamides (e.g., PA6I / 6T) or semi-crystalline PA66 / 6 (or PA66, PA6, PA9T, or PA66 / 6C) polyamides with specific A / C ratios in improving high-temperature damping and noise isolation has not been previously understood. The improved damping performance is reflected not only in the higher maximum tan(δ) temperature, but also in the higher maximum tan(δ) viscoelastic value in many cases. Importantly, because mechanical properties such as strength and impact resistance are maintained at high levels (previously observed only in the absence of amorphous or PA66 / 6I polyamide additives), the provided composition is particularly suitable for applications requiring both high stability and high damping.

[0023] Furthermore, because other thermal properties are similarly maintained at levels comparable to those of formulations without amorphous (PA6I / 6T) or semi-crystalline (PA66, PA6, PA66 / 6, and / or PA9T) polyamide additives, the provided compositions also exhibit good compatibility with existing manufacturing processes, such as molding and thermoforming processes. Additionally, in some embodiments, the heat distortion temperature (HDT) of the composition is close to the melt temperature (Tm) of the composition. m For example, below 45°C or below 35°C. This is because the T of the polymer composition... m The HDT of the polymer composition is largely unaffected by the presence of other fillers and additives in the composition, and the HDT of the polymer composition typically increases with increasing filler loading level. Therefore, the HDT and T of some embodiments of the disclosed reinforced compositions are... m Similarity between them can provide another benefit related to processability.

[0024] Overall performance is particularly important for certain applications (e.g., the aforementioned automotive parts) that connect one automotive component to another during use, such as mounting an engine to a chassis. In these applications, the ability of the parts (made from the disclosed NVH composition) to effectively isolate vibrations results in quiet performance. Conventional connecting parts typically use rubber components, often in conjunction with multiple rigid structural (metal) components, to achieve similar performance. It is believed that when the disclosed NVH composition is used for connecting parts, this multi-piece construction can be reduced / avoided, which reduces / eliminates the number / size of multiple parts, thereby improving manufacturing efficiency.

[0025] In some embodiments, this disclosure relates to polyamide compositions comprising one or more amorphous polyamides and one or more semi-crystalline polyamides. In some embodiments, this disclosure relates to polyamide compositions comprising a first semi-crystalline (co)polyamide, such as PA66 / 6, PA66, PA6, PA9T (co)polyamide, and a second semi-crystalline polyamide and / or amorphous polyamide (PA6I / 6T). Optionally, these compositions of the invention contain more than two semi-crystalline polyamides, such as three or four different semi-crystalline polyamides, and at least one amorphous polyamide, namely PA6I / 6T. These polyamide compositions have been found to provide improvements in high-temperature damping and noise isolation. According to industry standards, these polyamide compositions have been found to exhibit improved plasticity and / or processability. For example, the compositions have a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in the temperature range of 20°C to 180°C, such as at temperatures above 60°C. Preferably, above 60°C, for example above 65.4°C, optionally when the composition has a moisture content of less than 0.2% by weight.

[0026] Surprisingly, polyamide compositions of amorphous and semi-crystalline polyamides having the A / C ratios disclosed herein exhibit very high loss factors above 0.05 (>0.15, further >0.3, further >0.4, further >0.5, further >0.6, further >0.65, further >0.7, further up to 0.75) in a temperature range of 20°C to 180°C, such as 65.4°C to 113.9°C. The polyamide compositions of the present invention comprise: one or more amorphous polyamides; one or more semi-crystalline polyamides; reinforcing fibers; impact modifiers; and additives; wherein the compositions have a peak loss factor of 0.19 to 0.75 in a temperature range of 20°C to 180°C, for example, above 60°C. For example, 65°C to 115°C. In one specific embodiment, the polyamide composition of the present invention comprises: one or more amorphous polyamides; one or more semi-crystalline polyamides; reinforcing fibers; an impact modifier; and additives; wherein the composition has a peak loss factor of 0.60 to 0.75 in a temperature range of 20°C to 180°C, i.e., above 60°C and from 86°C to 96°C. In some embodiments, the polyamide composition comprises: 10% to 90% by weight of one or more amorphous polyamides; 5% to 80% by weight of one or more semi-crystalline polyamides; 10% to 70% by weight of reinforcing filler; 0% to 30% by weight of impact modifier; and 0.01% to 10% by weight of additives; wherein the composition has a peak loss factor above 0.15 in a temperature range of 20°C to 180°C.

[0027] In some implementations, the reinforcing filler is treated with a surface sizing agent.

[0028] In some embodiments, the compositions disclosed herein contain 0% to 30% by weight of at least one impact modifier. In one exemplary embodiment, the impact modifier is a polyolefin elastomer, including anhydride-modified ethylene copolymers. In one aspect, the polyolefin elastomer is FUSABOND 493. ® .

[0029] In some embodiments, the polyamide composition of 30% to ≤100% by weight comprises: 10% to 90% by weight of at least one amorphous polyamide (A); 10% to 80% by weight of at least one semi-crystalline polyamide (C); and 10% to 70% by weight of at least one reinforcing filler (F).

[0030] Composition

[0031] amorphous polyamide

[0032] In one aspect, a polyamide composition comprising one or more amorphous polyamides is disclosed. As used herein, the term "polyamide" or "nylon" refers to a polymer containing at least 50 mol%, for example, at least 60 mol%, at least 70 mol%, at least 80 mol%, at least 90 mol%, at least 92 mol%, at least 94 mol%, at least 96 mol%, at least 98 mol%, or at least 99 mol% of repeating units comprising at least one amide group. As used herein, the term "amorphous polyamide" refers to a polyamide that substantially does not contain crystalline regions, for example, does not contain crystalline regions and does not exhibit a clear melting point. The composition also comprises one or more semi-crystalline polyamides. As used herein, the term "semi-crystalline polyamide" refers to a polyamide that contains at least one crystalline region and exhibits a clear melting point.

[0033] These polyamide compositions have been found to provide improvements in high-temperature damping. For example, optionally when the composition has a moisture content of less than 0.2% by weight, using a specific A / C ratio, the composition exhibits a maximum viscoelastic loss factor (tan(δ)) at the temperatures described above and herein. In some embodiments, optionally when the composition has a moisture content of less than 0.2% by weight, the composition further has a T... m HDT with a phase difference of less than 35°C. Other performance characteristics are discussed below.

[0034] In some embodiments, the combined concentration of one or more amorphous polyamides in the composition is in the range of 3% to 90% by weight, for example, 3% to 80% by weight, 3% to 70% by weight, 3% to 65% by weight, 3% to 60% by weight, 5% to 55% by weight, 3% to 53% by weight, 3% to 33% by weight, 7% to 32% by weight, 8% to 38% by weight, 13% to 43% by weight, 18% to 48% by weight, 30% to 60% by weight, or 23% to 53% by weight. The combined concentration of amorphous polyamides can be in the range of 8 wt% to 40 wt%, 13 wt% to 65 wt%, 13 wt% to 50 wt%, 13.9 wt% to 50.0 wt%, for example 8 wt% to 27.2 wt%, 11.2 wt% to 30.4 wt%, 14.4 wt% to 33.6 wt%, 17.6 wt% to 36.8 wt%, 20.8 wt% to 40 wt%, or 32 wt% to 38 wt%. In terms of upper limits, the concentration of amorphous polyamide can be less than 90 wt%, 80 wt%, or 75 wt%, for example, less than 70 wt%, less than 65 wt%, less than 60 wt%, less than 50 wt%, less than 55 wt%, less than 53 wt%, less than 48 wt%, less than 43 wt%, less than 40 wt%, less than 38 wt%, less than 36.8 wt%, less than 33.6 wt%, less than 32 wt%, less than 30.4 wt%, less than 27.2 wt%, less than 24 wt%, less than 20.8 wt%, less than 17.6 wt%, less than 14.4 wt%, less than 13.9 wt%, less than 11.2 wt%, or less than 8 wt%. Regarding the lower limit, the concentration of amorphous polyamide can be greater than 3% by weight, for example greater than 7% by weight, greater than 10% by weight, greater than 11.2% by weight, greater than 13% by weight, greater than 13.9% by weight, greater than 14.4% by weight, greater than 17.6% by weight, greater than 20.8% by weight, greater than 24% by weight, greater than 27.2% by weight, greater than 30.4% by weight, greater than 32% by weight, greater than 33.6% by weight, greater than 36.8% by weight, greater than 40% by weight, greater than 43% by weight, or greater than 48% by weight. Higher concentrations, such as greater than 38% by weight, and lower concentrations, such as less than 3% by weight, are also considered.

[0035] In this invention, the combined concentration of one or more amorphous polyamides in the composition is from 10% to 90% by weight, for example, from 13% to 65% by weight, from 13% to 50% by weight, or from 13.9% to 50.0% by weight, including the range of 32% to 38% by weight. In some embodiments, at least one of the one or more amorphous polyamides has a glass transition temperature (T0) greater than 100°C (ranging from 100°C to 150°C). g ).

[0036] As used herein, the limitations of "greater than" and "less than" may also include the numbers associated with them. In other words, "greater than" and "less than" can be interpreted as "greater than or equal to" and "less than or equal to". It is contemplated that this language can be subsequently modified in the claims to include "or equal to". For example, "greater than 4.0" can be interpreted and subsequently modified in the claims to "greater than or equal to 4.0".

[0037] In some embodiments, the concentration of the amorphous polyamide is in the range of 4 wt% to 32 wt%, for example, 4 wt% to 20.8 wt%, 6.8 wt% to 23.6 wt%, 9.6 wt% to 26.4 wt%, 12.4 wt% to 29.2 wt%, or 15.2 wt% to 32 wt%, or 13.9 wt% to 50 wt%, such as 32 wt% to 38 wt%. At the upper limit, the concentration of the amorphous polyamide can be less than 38 wt%, less than 32 wt%, for example, less than 29.2 wt%, less than 26.4 wt%, less than 23.6 wt%, less than 20.8 wt%, less than 18 wt%, less than 15.2 wt%, less than 12.4 wt%, less than 9.6 wt%, or less than 6.8 wt%. Regarding the lower limit, the concentration of amorphous polyamide can be greater than 4% by weight, for example, greater than 6.8% by weight, greater than 9.6% by weight, greater than 12.4% by weight, greater than 15.2% by weight, greater than 18% by weight, greater than 20.8% by weight, greater than 23.6% by weight, greater than 26.4% by weight, greater than 29.2% by weight, or greater than 32% by weight. Higher concentrations, such as greater than 38% by weight, and lower concentrations, such as less than 4% by weight, are also considered.

[0038] In some embodiments, the concentration of the amorphous polyamide is in the range of 10 wt% to 70 wt%, for example, 15 wt% to 60 wt%, 15 wt% to 50 wt%, 20 wt% to 45 wt%, 25 wt% to 40 wt%, 30 wt% to 40 wt%, or 30 wt% to 37 wt%. At the upper limit, the concentration of the amorphous polyamide can be less than 70 wt%, for example, less than 65 wt%, less than 60 wt%, less than 65 wt%, less than 55 wt%, less than 50 wt%, less than 45 wt%, less than 40 wt%, or less than 37 wt%. At the lower limit, the concentration of the amorphous polyamide can be greater than 10 wt%, for example, greater than 15 wt%, greater than 20 wt%, greater than 25 wt%, greater than 27 wt%, greater than 30 wt%, or greater than 31 wt%. Higher concentrations, such as greater than 70 wt%, and lower concentrations, such as less than 10 wt%, are also considered.

[0039] In some embodiments, the amorphous polyamide comprises a polyamide having an isophthalic acid and / or terephthalic acid content. For example, the amorphous polyamide may include one or more of the following: PA6I / 6T; PA-4T / 4I; PA-4T / 6I; PA 5T / 5I; PA-6,6 / 6T; PA-6T / 6I; PA-6T / 6l / 6; PA-6T / 6; PA-6T / 6l / 66; PA-6T / 66; PA-6l / 6T, PA-6T / 6; PA 6,6 / 6l / 6; PA-6l / 6; or 6T / 6l / 6, PA-6T / 610; PA-10T / 612; PA-10T / 106; PA-6T / 612; PA-6T / 10T; PA 6T / 10I; PA-9T; PA-10T; PA-12T; PA-10T / 10I; PA-10T / 12; PA-10T / 11; PA-6T / 9T; PA-6T / 12T; PA 6T / 10T / 6I; PA-6T / 6I / 6; PA-6T / 6I / 12; MPMD-T; MPMD-I; or blends of polyamides with MPMD-T / MPMD I, such as DT / DI blends; or combinations thereof. In some cases, the amorphous or semi-crystalline nature of the polyamide may depend on the percentage of various polymer units. In some cases, the above-described polyamides may be formulated as “amorphous” (A) or “semi-crystalline” (C) as defined herein. In some embodiments, these polyamides may be semi-crystalline or amorphous, depending on the polymer units. Those skilled in the art will understand how to determine the amorphous or semi-crystalline (as defined herein) nature of a polymer. For example, if PA-6I / 6T polyamide is formulated such that it substantially does not contain crystalline regions, for example, does not contain crystalline regions, and does not exhibit a distinct melting point, then PA-6I / 6T will be considered "amorphous PA-6I / 6T". In this invention, at least one amorphous polyamide includes PA6I / 6T.

[0040] In some cases, the molar ratio of isophthalic acid to terephthalic acid in amorphous polyamides can be, for example, from 37:63 to 85:15, or from 37:63 to 70:30, 43:57 to 75:25, 48:52 to 79:21, 54:46 to 82:18, or 60:40 to 85:15. At the upper limit, the ratio of isophthalic acid to terephthalic acid can be less than 85:15, for example, less than 82:18, less than 79:21, less than 75:25, less than 70:30, less than 65:35, less than 60:40, less than 54:46, less than 48:52, or less than 43:57. With regard to the lower limit, the ratio of isophthalic acid to terephthalic acid can be greater than 37:63, for example greater than 43:57, greater than 48:52, greater than 54:46, greater than 60:40, greater than 65:35, greater than 70:30, greater than 75:25, greater than 79:81, or greater than 82:18. Higher ratios, such as greater than 85:15, and lower ratios, such as less than 37:63, are also considered. Exemplary commercial amorphous polyamide products suitable for the provided compositions include GRIVORY from EMS Chemie. ® G-21 and SELAR from DuPont ® PA3426.

[0041] The number of different types of amorphous polyamides in the provided composition can be, for example, one, two, three, four, five, six, seven, eight, nine, ten, or more than ten. In some embodiments, one or more amorphous polyamides in the composition comprise partially aromatic polyamides. In some embodiments, each amorphous polyamide in the composition is a partially aromatic polyamide. In some embodiments, one or more amorphous polyamides comprise amorphous copolyimides. In some embodiments, each amorphous polyamide is an amorphous copolyimide.

[0042] In some embodiments, the amorphous polyamide of the composition is a partially aromatic polyamide. In some embodiments, the amorphous polyamide is an amorphous copolyamide. In some embodiments, the amorphous polyamide is transparent. The use of amorphous polyamides may be particularly advantageous, for example, in applications requiring the observation of liquid levels, food packaging, or other materials enclosed or separated by polymeric materials made using the composition.

[0043] In some cases, the chemical properties of the polymer composition (or one or more of its components) contribute at least in part to the performance improvement. The characteristics of the disclosed compositions and parts may lie in their chemical properties, independent of the compositional structure of the polymer composition (e.g., polyamide alone). In some cases, the composition contains T g High T for 100℃ to 200℃g Polymers and T g Low T from 0℃ to 160℃ g polymer.

[0044] In some embodiments, at least one amorphous polyamide (with little or no moisture content) in the composition has a glass transition temperature (Tg) in the range of 100°C to 200°C, for example, 100°C to 175°C, 100°C to 150°C, 100°C to 130°C, 105°C to 135°C, 110°C to 140°C, 115°C to 145°C, or 120°C to 150°C. g In terms of the upper limit, the T of amorphous polyamides... g It can be below 200℃, for example, below 175℃, below 150℃, below 145℃, below 140℃, below 135℃, below 130℃, below 125℃, below 120℃, below 115℃, below 110℃, or below 105℃. Regarding the lower limit, the T of amorphous polyamide... g The temperature can be greater than 100°C, for example, greater than 105°C, greater than 110°C, greater than 115°C, greater than 120°C, greater than 125°C, greater than 130°C, greater than 135°C, greater than 140°C, or greater than 145°C. In some embodiments, each amorphous polyamide in the composition independently has a Tg in the range of 100°C to 150°C as described herein. g Higher temperatures, such as above 150°C, and lower temperatures, such as below 100°C, were also considered.

[0045] These ranges and limitations also apply to the aforementioned high-T g polymer.

[0046] In some implementations, low T g The polymer has a T value in the range of 0°C to 160°C, for example, 10°C to 120°C, 20°C to 100°C, 30°C to 90°C, or 40°C to 90°C. g In terms of the upper limit, low T g The polymer can have a T value less than 160°C, for example less than 140°C, less than 120°C, less than 100°C, less than 90°C, less than 80°C, or less than 70°C. g Regarding the lower limit, low T g The polymer can have a T value greater than 0°C, for example, greater than 10°C, greater than 20°C, greater than 30°C, greater than 40°C, greater than 50°C, or greater than 60°C. g .

[0047] In some embodiments, at least one amorphous polyamide in the composition has a flexural / tensile modulus in the range of 2.6 GPa to 3.2 GPa, for example, 2.6 GPa to 2.96 GPa, 2.66 GPa to 3.02 GPa, 2.72 GPa to 3.08 GPa, 2.78 GPa to 3.14 GPa, or 2.84 GPa to 3.2 GPa. At the upper limit, the tensile modulus of the amorphous polyamide may be less than 3.2 GPa, for example, less than 3.14 GPa, less than 3.08 GPa, less than 3.02 GPa, less than 2.96 GPa, less than 2.9 GPa, less than 2.84 GPa, less than 2.78 GPa, less than 2.72 GPa, or less than 2.66 GPa. With regard to the lower limit, the flexural modulus of the amorphous polyamide can be greater than 2.6 GPa, for example greater than 2.66 GPa, greater than 2.72 GPa, greater than 2.78 GPa, greater than 2.84 GPa, greater than 2.9 GPa, greater than 2.96 GPa, greater than 3.02 GPa, greater than 3.08 GPa, or greater than 3.14 GPa. In some embodiments, each amorphous polyamide in the composition can independently have a tensile modulus in the range of 2.6 GPa to 3.2 GPa as described herein. Higher tensile moduli, such as greater than 3.2 GPa, and lower tensile moduli, such as less than 2.6 GPa, are also considered.

[0048] In some embodiments, at least one amorphous polyamide in the composition may have a tensile modulus in the range of 8.78 GPa to 17 GPa, for example, 9.59 GPa, 10.9 GPa, 11 GPa, 11.4 GPa, 11.5 GPa, 11.6 GPa, 11.7 GPa, 11.8 GPa, 11.9 GPa, and 14.4 GPa.

[0049] In some embodiments, at least one of the amorphous polyamides in the composition has a content of 1.16 g / cm³. 3 Up to 1.21 g / cm 3 For example, 1.17 g / cm³ 3 Up to 1.19 g / cm³, 1.165 g / cm³ 3 Up to 1.195 g / cm 3 1.17 g / cm 3 Up to 1.2 g / cm 3 1.175g / cm 3 Up to 1.205 g / cm 3 Or 1.18 g / cm 3 Up to 1.21 g / cm 3 Density within a certain range. At the upper limit, the density of amorphous polyamide can be less than 1.21 g / cm³. 3For example, less than 1.205 g / cm³ 3 Less than 1.2 g / cm 3 Less than 1.195 g / cm³ 3 Less than 1.19 g / cm³ 3 Less than 1.185 g / cm³ 3 Less than 1.18 g / cm 3 Less than 1.175 g / cm³ 3 Less than 1.17 g / cm³ 3 or less than 1.165 g / cm 3 Regarding the lower limit, the density of amorphous polyamide can be greater than 1.16 g / cm³. 3 For example, greater than 1.165 g / cm³ 3 Greater than 1.17 g / cm 3 Greater than 1.175 g / cm³ 3 Greater than 1.18 g / cm 3 Greater than 1.185 g / cm 3 Greater than 1.19 g / cm 3 Greater than 1.195 g / cm³ 3 Greater than 1.2 g / cm 3 or greater than 1.205 g / cm 3 In some embodiments, each amorphous polyamide in the composition may independently have a content of 1.16 g / cm³ as described herein. 3 Up to 1.21 g / cm 3 Densities within the specified range. Higher densities, such as greater than 1.21 g / cm³, were also considered. 3 and lower density, such as less than 1.16 g / cm³. 3 .

[0050] Blends of polyamide with MPMD-T / MPMD-1 (DT / DI)

[0051] In some cases, amorphous polyamides include blends of polyamides with MPMD-T / MPMD-1 (e.g., DT / DI). In some cases, the use of DT / DI is particularly advantageous. Without being bound by theory, the T0 of DT / DI... g In polyamide compositions, DT / DI works in conjunction with semi-crystalline polyamides. In some cases, DT / DI can be used in smaller amounts (relative to some other amorphous polyamides) while still achieving similar or better NVH performance. Advantageously, it has also been found that smaller amounts of DT / DI (e.g., those disclosed herein) may be required to provide the desired NVH improvement. Therefore, larger amounts of higher-performance polymers can be used, which contributes to favorable mechanical property improvements (and NVH improvements). DT / DI can be present in the amounts described above.

[0052] Exemplary commercial products of DT / DI-based amorphous polyamides suitable for the provided compositions include SVPx-129 Novadyn DT / DI from Shakespeare.

[0053] In some embodiments, at least one of the amorphous polyamides comprises an amorphous copolyamide. In some embodiments, the amorphous polyamide comprises a polyamide blend of MPMD-T and MPMD-I, and / or the semi-crystalline polyamide comprises PA66 / 6C.

[0054] semi-crystalline polyamide

[0055] The number of different types of semi-crystalline polyamides in the composition can be, for example, one, two, three, four, five, six, seven, eight, nine, ten, or more than ten. In some embodiments, one or more semi-crystalline polyamides in the composition include PA66 polyamide, PA6 polyamide, PA66 / 6 polyamide, or PA66 / 6I polyamide, or combinations thereof.

[0056] As used herein, the terms “PA66,” “Nylon 66,” and “Polyamide 66” refer to homopolymers prepared from hexamethylenediamine and adipic acid monomer subunits. PA66 polyamide can be a polyamide containing a significant portion (e.g., at least 5 wt%, at least 10 wt%, at least 14 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, or at least 90 wt%) of PA66 units in the polymer backbone. As used herein, the terms “PA6,” “Nylon 6,” and “Polyamide 6” refer to homopolymers prepared from caprolactam monomer subunits. As used herein, the terms “PA66 / 6,” “Nylon 66 / 6,” and “Polyamide 66 / 6” refer to copolymers prepared from hexamethylenediamine and adipic acid monomer subunits and also incorporating caprolactam monomer subunits. As used herein, the terms “PA66 / 6I”, “Nylon 66 / 6I”, and “Polyamide 66 / 6I” refer to copolymers prepared from hexamethylenediamine and adipic acid monomer subunits and also incorporated with isophthalic acid monomer subunits.

[0057] The semi-crystalline polyamides in the composition may include, for example, PA66; PA6; PA66 / 6; PA66 / 6T; PA66 / 6I; PA66 / 6C; PA9T; PA10T; PA12T; or PA-6T / 9T; or combinations or copolymers thereof. This list is not intended to limit the range of semi-crystalline polyamides.

[0058] Exemplary combinations include PA66 and PA6; PA66 and PA66 / 6; PA66 and PA66 / 6I; PA6 and PA66 / 6; PA6 and PA66 / 6I; PA6 and PA66 / 6C; PA66 / 6 and PA66 / 6I; PA66, PA6 and PA66 / 6; PA66, PA6, PA66 / 6C; and PA66, PA66 / 6, PA66 / 6C and PA66 / 6I; or PA66, PA6, PA66 / 6 and PA66 / 6I. In one embodiment, the semi-crystalline polyamide comprises at least one selected from the group consisting of PA66, PA6, PA66 / 6 and PA9T.

[0059] In some embodiments, the concentration of one or more semi-crystalline polyamides is in the range of 30 wt% to 80 wt%, for example, 30 wt% to 60 wt%, 31 wt% to 63 wt%, 35 wt% to 65 wt%, 31 wt% to 55 wt%, 40 wt% to 70 wt%, 45 wt% to 75 wt%, or 50 wt% to 80 wt%. With respect to the upper limit, the concentration of semi-crystalline polyamide can be less than 80 wt%, for example, less than 75 wt%, less than 70 wt%, less than 65 wt%, less than 60 wt%, less than 55 wt%, less than 50 wt%, less than 45 wt%, less than 40 wt%, or less than 35 wt%. With respect to the lower limit, the concentration of semi-crystalline polyamide can be greater than 30 wt%, for example, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, greater than 55 wt%, greater than 60 wt%, greater than 65 wt%, greater than 70 wt%, or greater than 75 wt%. Higher concentrations, such as greater than 80 wt%, and lower concentrations, such as less than 30 wt%, are also considered.

[0060] In some embodiments, the concentration of one or more semi-crystalline polyamides (e.g., PA66) is in the range of 10 wt% to 70 wt%, for example, 15 wt% to 60 wt%, 15 wt% to 50 wt%, 20 wt% to 45 wt%, 30 wt% to 45 wt%, 25 wt% to 40 wt%, 30 wt% to 40 wt%, or 30 wt% to 37 wt%. At the upper limit, the semi-crystalline polyamide concentration can be less than 70 wt%, for example, less than 65 wt%, less than 60 wt%, less than 65 wt%, less than 55 wt%, less than 50 wt%, less than 45 wt%, less than 40 wt%, or less than 37 wt%. At the lower limit, the semi-crystalline polyamide concentration can be greater than 10 wt%, for example, greater than 15 wt%, greater than 20 wt%, greater than 25 wt%, greater than 27 wt%, greater than 30 wt%, or greater than 31 wt%. Higher concentrations, such as greater than 70 wt%, and lower concentrations, such as less than 10 wt%, are also considered.

[0061] In some embodiments, the combined concentration of one or more semi-crystalline polyamides in the composition is in the range of 5% to 80% by weight, for example 10% to 80% by weight, 10% to 70% by weight, 10% to 65% by weight, 14% to 65% by weight, or 14.55% to 64.55% by weight, including the range of 26% to 32% by weight or 26.55% to 32.55% by weight.

[0062] In some embodiments, at least one of the semi-crystalline polyamides is PA66 polyamide. In some embodiments, at least one of the semi-crystalline polyamides is PA6 polyamide. In some embodiments, at least one of the semi-crystalline polyamides is PA66 / 6, PA66 / 6 (co)polyamide, PA9T, and / or PA66 / 6C. In some embodiments, at least one of the semi-crystalline polyamides is PA9T. In some embodiments, at least one of the semi-crystalline polyamides is PA66 / 6I polyamide. In some embodiments, at least one of the semi-crystalline polyamides in PA66 / 6I polyamide has an isophthalic acid content in the range of 5 mol% to 13 mol%.

[0063] PA66 / 6 (co)polyamide

[0064] PA66 / 6 (co)polyamide is an example of a semi-crystalline polymer, and it can be used as discussed herein.

[0065] On one hand, polyamide compositions comprising other semi-crystalline polyamides as described above, as well as semi-crystalline PA66 / 6 copolyamides, are disclosed. In some cases, the composition further comprises PA66 / 6 copolyamide and: 1) a second semi-crystalline polyamide, or 2) an amorphous polyamide. It has been found that the polyamide compositions provide the improvements described above. For example, optionally when the composition has a moisture content of less than 0.2% by weight, the composition exhibits a maximum viscoelastic loss factor (tan(δ)) at high temperatures, in the temperature range of 20°C–180°C, for example, above 40°C, above 60°C, or above 72°C.

[0066] In some embodiments, the concentration of the semi-crystalline PA66 / 6 copolyamide in the composition is in the range of 1 wt% to 50 wt%, for example, 5 wt% to 40 wt%, 5 wt% to 30 wt%, 7 wt% to 30 wt%, 7 wt% to 25 wt%, or 10 wt% to 20 wt%. At the upper limit, the PA66 / 6 copolyamide concentration can be less than 50 wt%, for example, less than 40 wt%, less than 35 wt%, less than 30 wt%, less than 25 wt%, less than 20 wt%, or less than 17 wt%. At the lower limit, the PA66 / 6 copolyamide concentration can be greater than 5 wt%, for example, greater than 7 wt%, greater than 9 wt%, greater than 10 wt%, greater than 12 wt%, greater than 13 wt%, or greater than 14 wt%. Higher concentrations, such as greater than 70 wt%, and lower concentrations, such as less than 30 wt%, are also considered.

[0067] In some embodiments, the concentration of the semi-crystalline PA66 / 6 copolyamide is in the range of 4 wt% to 32 wt%, for example, 4 wt% to 20.8 wt%, 6.8 wt% to 23.6 wt%, 9.6 wt% to 26.4 wt%, 12.4 wt% to 29.2 wt%, or 15.2 wt% to 32 wt%. At the upper limit, the concentration of the semi-crystalline PA66 / 6 copolyamide can be less than 32 wt%, for example, less than 29.2 wt%, less than 26.4 wt%, less than 23.6 wt%, less than 20.8 wt%, less than 18 wt%, less than 15.2 wt%, less than 12.4 wt%, less than 9.6 wt%, or less than 6.8 wt%. Regarding the lower limit, the concentration of semi-crystalline PA66 / 6 copolyamide can be greater than 4% by weight, for example, greater than 6.8% by weight, greater than 9.6% by weight, greater than 12.4% by weight, greater than 15.2% by weight, greater than 18% by weight, greater than 20.8% by weight, greater than 23.6% by weight, greater than 26.4% by weight, or greater than 29.2% by weight. Higher concentrations, such as greater than 32% by weight, and lower concentrations, such as less than 4% by weight, have also been considered.

[0068] PA66 / 6I

[0069] PA66 / 6I is an example of a semi-crystalline polymer, and it can be used as discussed herein. On the other hand, polyamide compositions comprising the semi-crystalline PA66 / 6I copolyamide are disclosed. It has been found that the polyamide compositions provide improvements in high-temperature damping. For example, optionally when the composition has a moisture content of less than 0.2% by weight, the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in the temperature range of 20°C–180°C, i.e., above 60°C or 72°C.

[0070] In some embodiments, the concentration of the semi-crystalline PA66 / 6I copolyamide in the composition is in the range of 30 wt% to 70 wt%, for example, 30 wt% to 54 wt%, 34 wt% to 58 wt%, 38 wt% to 62 wt%, 46 wt% to 55 wt%, 42 wt% to 66 wt%, or 46 wt% to 70 wt%. With respect to the upper limit, the PA66 / 6I concentration can be less than 70 wt%, for example, less than 66 wt%, less than 62 wt%, less than 58 wt%, less than 54 wt%, less than 50 wt%, less than 46 wt%, less than 42 wt%, less than 38 wt%, or less than 34 wt%. With respect to the lower limit, the PA66 / 6I concentration can be greater than 30 wt%, for example, greater than 34 wt%, greater than 38 wt%, greater than 42 wt%, greater than 46 wt%, greater than 50 wt%, greater than 54 wt%, greater than 58 wt%, greater than 62 wt%, or greater than 66 wt%. Higher concentrations, such as greater than 70 wt%, and lower concentrations, such as less than 30 wt%, are also considered.

[0071] In some embodiments, the composition comprises PA66 / 6I polyamide having an isophthalic acid content ranging from 5 mol% to 30 mol%, for example, 5 mol% to 20 mol%, 7.5 mol% to 22.5 mol%, 10 mol% to 25 mol%, 12.5 mol% to 27.5 mol%, or 15 mol% to 30 mol%. At the upper limit, the isophthalic acid content of PA66 / 6I polyamide can be less than 30 mol%, for example, less than 27.5 mol%, less than 25 mol%, less than 22.5 mol%, less than 20 mol%, less than 17.5 mol%, less than 15 mol%, less than 12.5 mol%, less than 10 mol%, or less than 7.5 mol%. With regard to the lower limit, the isophthalic acid content of PA66 / 6I polyamide can be greater than 5 mol%, for example greater than 7.5 mol%, greater than 10 mol%, greater than 12.5 mol%, greater than 15 mol%, greater than 17.5 mol%, greater than 20 mol%, greater than 22.5 mol%, greater than 25 mol%, or greater than 27.5 mol%. In some embodiments, each PA66 / 6I polyamide in the composition independently has an isophthalic acid content in the range of 5 mol% to 30 mol% as disclosed herein. Higher contents, such as greater than 30 mol%, and lower contents, such as less than 5 mol%, are also considered.

[0072] In some embodiments, the ratio of the combined weight of one or more semi-crystalline polyamides in the composition to the combined weight of one or more amorphous polyamides in the composition is in the range of 0.01:1 to 20:1, for example 0.05:1 to 18:1; 0.05:1 to 15:1, 0.06:1 to 13:1, 0.1:1 to 13:1, 0.5:1 to 12:1, 0.75:1 to 12:1, 1:1 to 13:1, 1:1 to 4.7:1, 1.3:1 to 6:1, 1.7:1 to 7.8:1, 2.2:1 to 10:1, or 2.8:1 to 13:1. Regarding the upper limit, the weight ratio of semi-crystalline polyamide to amorphous polyamide can be less than 20:1, for example, less than 18:1, less than 15:1, less than 10:1, less than 7.8:1, less than 6:1, less than 4.7:1, less than 3.6:1, less than 2.8:1, less than 2.2:2, less than 1.7:1, or less than 1.3:1. Regarding the lower limit, the weight ratio of semi-crystalline polyamide to amorphous polyamide can be greater than 0.01:1, for example, greater than 0.05:1, greater than 0.06:1, greater than 0.1:1, greater than 0.5:1, greater than 0.75:1, greater than 1:1, greater than 1.3:1, greater than 1.7:1, greater than 2.2:1, greater than 2.8:1, greater than 3.6:1, greater than 4.7:1, greater than 6:1, greater than 7.8:1, or greater than 10:1. Higher ratios, such as greater than 13:1, and lower ratios, such as less than 1:1, are also considered. These ranges and limitations generally and individually apply to semi-crystalline polyamides and amorphous polyamides, such as PA66 / 6I or PA66 / 6C.

[0073] PA66 / 6C

[0074] PA66 / 6C is an example of a semi-crystalline polymer, and it can be used as discussed herein. In one embodiment, the C of PA66 / 6C is a 1,4-cyclohexanediol (CHDA) monomer unit. In some embodiments, polyamide compositions comprising a semi-crystalline PA66 / 6C copolymer are disclosed. In some cases, the semi-crystalline polyamide (of the polyamide composition) comprises PA66 / 6C. PA66 / 6C can be used alone or in combination with other semi-crystalline polyamides, examples of which are disclosed herein.

[0075] In some cases, polyamide compositions have been found to provide improvements in high-temperature damping. For example, when the composition has a moisture content of less than 0.2% by weight, the composition exhibits the maximum viscoelastic loss factor (tan(δ)) at the aforementioned temperature.

[0076] It has been found that semi-crystalline polyamides (e.g., PA66 / 6C) interact with amorphous polyamides. For example, semi-crystalline polyamides advantageously balance (e.g., reduce) some of the effects of amorphous polyamides. The combination of semi-crystalline polyamides and amorphous polyamides (e.g., PA66 / 6C) provides improvements in NVH performance and mechanical properties (e.g., stiffness).

[0077] In some cases, semi-crystalline polyamides have been found to improve stiffness properties (e.g., tensile modulus) that may be associated with the content of amorphous polymers. This unexpected improvement may be particularly noticeable when measured at (operating) temperatures (e.g., the temperatures at which the polyamide composition is used).

[0078] It has also been found that when using some semi-crystalline polyamides (e.g., PA66 / 6C), a smaller amount of the semi-crystalline polyamide (e.g., the smaller amount disclosed herein) may be required to provide the desired improvement. Therefore, a larger amount of the higher-performance polymer can be used, which contributes to a favorable improvement in mechanical properties.

[0079] Unbound by theory, it is assumed that the non-aromatic (planar) structure of PA66 / 6C allows it to crystallize / co-crystallize better with acids (e.g., adipic acid) in other polyamides, especially compared to some aromatic polyamides that do not possess this planar structure and are therefore less likely to crystallize / co-crystallize with acids. This crystallization is believed to provide the aforementioned advantageous performance benefits (provided by the combination of semi-crystalline and amorphous polyamides).

[0080] In some embodiments, the concentration of PA66 / 6C is in the range of 10 wt% to 70 wt%, for example, 15 wt% to 60 wt%, 15 wt% to 50 wt%, 20 wt% to 45 wt%, 25 wt% to 40 wt%, 25 wt% to 30 wt%, 30 wt% to 40 wt%, 30 wt% to 37 wt%, or 28 wt% to 35 wt%. At the upper limit, the PA66 / 6C concentration can be less than 70 wt%, for example, less than 65 wt%, less than 60 wt%, less than 65 wt%, less than 55 wt%, less than 50 wt%, less than 45 wt%, less than 40 wt%, less than 37 wt%, or less than 35 wt%. At the lower limit, the PA66 / 6C concentration can be greater than 10 wt%, for example, greater than 15 wt%, greater than 20 wt%, greater than 25 wt%, greater than 27 wt%, greater than 28 wt%, greater than 30 wt%, or greater than 31 wt%. Higher concentrations, such as greater than 70 wt%, and lower concentrations, such as less than 10 wt%, have also been considered.

[0081] A / C ratio

[0082] In some embodiments, the amorphous polyamide (A) / semi-crystalline polyamide (C) ratio is from about 0.48 to about 0.67. In one aspect, the A / C ratio is not 0.50 or 0.51. In another aspect, the A / C ratio is about 0.48, or about 0.49, or about 0.52, or about 0.53, or about 0.54, or about 0.55, or about 0.56, or about 0.57, or about 0.58, or about 0.59, or about 0.60, or about 0.61, or about 0.62, or about 0.63, or about 0.64, or about 0.65, or about 0.66, or about 0.67.

[0083] In some implementations, the A / C ratio is from about 0.67 to about 0.98. In another aspect, the A / C ratio is not 0.79. In one respect, the A / C ratio is approximately 0.68, or approximately 0.69, or approximately 0.70, or approximately 0.71, or approximately 0.72, or approximately 0.73, or approximately 0.74, or approximately 0.75, or approximately 0.76, or approximately 0.77, or approximately 0.78, or approximately 0.80, or approximately 0.81, or approximately 0.82, or approximately 0.83, or approximately 0.84, or approximately 0.85, or approximately 0.86, or approximately 0.87, or approximately 0.88, or approximately 0.89, or approximately 0.90, or approximately 0.91, or approximately 0.92, or approximately 0.93, or approximately 0.94, or approximately 0.95, or approximately 0.96, or approximately 0.97, or approximately 0.98.

[0084] In some embodiments, the A / C ratio is from about 0.98 to about 1.43. In one aspect, the A / C ratio is not 1.00 to 1.02. For example, the A / C ratio is not 1.00, 1.01, or 1.02. In one aspect, the A / C ratio is about 0.99, or about 1.03, or about 1.04, or about 1.05, or about 1.06, or about 1.07, or about 1.08, or about 1.09, or about 1.10, or about 1.11, or about 1.12, or about 1.13, or about 1.14, or about 1.15, or about 1.16, or about 1.17, or about 1.18, or about 1.19, or about 1.20, or about 1.21, or Approximately 1.22, or approximately 1.23, or approximately 1.24, or approximately 1.25, or approximately 1.26, or approximately 1.27, or approximately 1.28, or approximately 1.29, or approximately 1.30, or approximately 1.31, or approximately 1.32, or approximately 1.33, or approximately 1.34, or approximately 1.35, or approximately 1.36, or approximately 1.37, or approximately 1.38, or approximately 1.39, or approximately 1.40, or approximately 1.41, or approximately 1.42, or approximately 1.43.

[0085] In some implementations, the A / C ratio is from about 1.43 to about 4.00, such as about 3.44. In one aspect, the A / C ratio is about 1.43, or about 1.44, or about 1.45, or about 1.46, or about 1.47, or about 1.48, or about 1.49, or about 1.50, or about 1.51, or about 1.52, or about 1.53, or about 1.54, or about 1.55, or about 1.56, or about 1.57, or about 1.58, or about 1.5... 9, or approximately 1.60, or approximately 1.61, or approximately 1.62, or approximately 1.63, or approximately 1.64, or approximately 1.65, or approximately 1.66, or approximately 1.67, or approximately 1.68, or approximately 1.69, or approximately 1.70, or approximately 1.71, or approximately 1.72, or approximately 1.73, or approximately 1.74, or approximately 1.75, or approximately 1.76, or approximately 1.77, or Approximately 1.78, or approximately 1.79, or approximately 1.80, or approximately 1.81, or approximately 1.82, or approximately 1.83, or approximately 1.84, or approximately 1.85, or approximately 1.86, or approximately 1.87, or approximately 1.88, or approximately 1.89, or approximately 1.90, or approximately 1.91, or approximately 1.92, or approximately 1.93, or approximately 1.94, or approximately 1.95, or approximately 1 .96, or about 1.97, or about 1.98, or about 1.99, or about 2.00, or about 2.01, or about 2.02, or about 2.03, or about 2.04, or about 2.05, or about 2.06, or about 2.07, or about 2.08, or about 2.09, or about 2.10, or about 2.11, or about 2.12, or about 2.13, or about 2.14.

[0086] In other embodiments, the A / C ratio is from about 2.14 to about 3.44. In one aspect, the A / C ratio is about 2.14, or about 2.15, or about 2.16, or about 2.17, or about 2.18, or about 2.19, or about 2.20, or about 2.21, or about 2.22, or about 2.23, or about 2.24, or about 2.25, or about 2.26, or about 2.27, or about 2.28, or about 2.29, or about 2.30, or about 2.31, or about 2.32, or about 2.33, or about 2.34, or about 2.35, or about 2.36, or about 2.37, or about 2.38, or about 2.39, or about 2.40, or about 2.41, or about 2.42, or about 2.43.

[0087] In some embodiments, the A / C ratio may be between 0.55 and 0.99, including a lower limit range of 0.67 to 0.98. In one aspect, the A / C ratio does not include 0.79. In another aspect of the invention, the A / C ratio may be between 1.05 and 4.00 or between 1.10 and 3.50, including an upper limit range of 1.43 to 3.44. In one embodiment, the A / C ratio is not any one or more of 0.14, 0.20, 0.33, 0.50, 0.51, 0.79, 1.00, 1.01, or 1.02.

[0088] In some embodiments, the weight percentage of one or more amorphous polyamides (A) in the composition to the weight percentage of one or more semi-crystalline polyamides (C) in the composition is greater than 0.40. In one embodiment, the A / C ratio is in the range of about 0.40 to about 4.0, or about 0.45 to 4.0. In one embodiment, the A / C ratio is about 0.45 to about 3.50, or about 0.45 to about 3.44. In one aspect, the A / C ratio is about 0.55 to about 0.99. In another aspect, the A / C ratio is about 1.05 to about 4.00. In one aspect, the A / C ratio is about 1.05 to about 3.50. In one embodiment, the A / C ratio is about 0.90 to about 1.50, about 0.90 to about 1.45, about 0.95 to about 1.43, or about 0.98 to about 1.43. In one embodiment, the A / C ratio is about 0.55 to about 0.99, for example, about 0.67 to about 0.98. In another embodiment, the A / C ratio is from about 1.10 to about 3.50, for example from about 1.43 to about 3.44.

[0089] A / F and C / F ratios

[0090] In some embodiments, the ratio of amorphous polyamide (A) to reinforcing fiber (F) (such as glass fiber) is from about 0.49 to about 2.00, or from about 0.49 to about 1.83. In one respect, the A / F ratio is approximately 0.49, or approximately 0.50, or approximately 0.51, or approximately 0.52, or approximately 0.53, or approximately 0.54, or approximately 0.55, or approximately 0.56, or approximately 0.57, or approximately 0.58, or approximately 0.59, or approximately 0.61, or approximately 0.62, or approximately 0.63, or approximately 0.64, or approximately 0.65, or approximately 0.66, or approximately 0.67, or approximately 0.68, or approximately 0.69, or approximately 0.70, or approximately 0.71, or approximately 0.72, or approximately 0.73, or approximately 0.74, or approximately 0.75, or approximately 0.76, or approximately 0.77, or approximately 0.78, or approximately 0.79, or approximately 0.81, or approximately 0. 82, or about 0.83, or about 0.84, or about 0.85, or about 0.86, or about 0.87, or about 0.88, or about 0.89, or about 0.92, or about 0.93, or about 0.94, or about 0.95, or about 0.96, or about 0.97, or about 0.98, or about 0.99, or about 1.00, or about 1.01, or about 1.02, or about 1.03, or about 1.04, or about 1.05, or about 1.06, or about 1.07, or about 1.08, or about 1.09, or about 1.10, or about 1.11, or about 1.12, or about 1.13, or about 1.14, or about 1.15, or about 1.16, or about 1.1 7, or approximately 1.18, or approximately 1.19, or approximately 1.20, or approximately 1.21, or approximately 1.22, or approximately 1.23, or approximately 1.24, or approximately 1.25, or approximately 1.26, or approximately 1.27, or approximately 1.28, or approximately 1.29, or approximately 1.30, or approximately 1.31, or approximately 1.32, or approximately 1.33, or approximately 1.34, or approximately 1.35, or approximately 1.36, or approximately 1.37, or approximately 1.38, or approximately 1.39, or approximately 1.40, or approximately 1.41, or approximately 1.42, or approximately 1.43, or approximately 1.44, or approximately 1.45, or approximately 1.46, or approximately 1.47, or approximately 1.48, or approximately 1.49, or approximately 1.50 Or approximately 1.51, or approximately 1.52, or approximately 1.53, or approximately 1.54, or approximately 1.55, or approximately 1.56, or approximately 1.57, or approximately 1.58, or approximately 1.59, or approximately 1.60, or approximately 1.61, or approximately 1.62, or approximately 1.63, or approximately 1.64, or approximately 1.65, or approximately 1.66, or approximately 1.67, or approximately 1.68, or approximately 1.69, or approximately 1.70, or approximately 1.71, or approximately 1.72, or approximately 1.73, or approximately 1.74, or approximately 1.75, or approximately 1.76, or approximately 1.77, or approximately 1.78, or approximately 1.79, or approximately 1.80, or approximately 1.81, or approximately 1.82, or approximately 1.83.

[0091] In some implementations, the amorphous polyamide (A) / reinforcing fiber (F) ratio is not 0.28. The A / F ratio is not 0.23, 0.30, 0.45, 0.60, 0.80, 0.90, or 0.91.

[0092] In some embodiments, the ratio of semi-crystalline polyamide (C) to reinforcing fiber (F) (such as glass fiber) is about 0.40 to about 2.00, or about 0.40 to about 1.83. In one respect, the C / F ratio is approximately 0.48, or approximately 0.49, or approximately 0.50, or approximately 0.51, or approximately 0.52, or approximately 0.53, or approximately 0.55, or approximately 0.56, or approximately 0.57, or approximately 0.58, or approximately 0.59, or approximately 0.61, or approximately 0.62, or approximately 0.63, or approximately 0.64, or approximately 0.65, or approximately 0.66, or approximately 0.67, or approximately 0.68, or approximately 0.69, or approximately 0.70, or approximately 0.71, or approximately 0.72, or approximately 0.73, or approximately 0.74, or approximately 0.75, or approximately 0.76, or approximately 0.77, or approximately 0.78, or approximately 0.79. Or approximately 0.81, or approximately 0.82, or approximately 0.83, or approximately 0.84, or approximately 0.85, or approximately 0.86, or approximately 0.87, or approximately 0.88, or approximately 0.90, or approximately 0.92, or approximately 0.93, or approximately 0.94, or approximately 0.95, or approximately 0.96, or approximately 0.97, or approximately 0.98, or approximately 0.99, or approximately 1.00, or approximately 1.02, or approximately 1.03, or approximately 1.04, or approximately 1.05, or approximately 1.06, or approximately 1.07, or approximately 1.08, or approximately 1.09, or approximately 1.10, or approximately 1.11, or approximately 1.12, or approximately 1.13, or approximately 1.14, or approximately 1.1 5, or approximately 1.16, or approximately 1.17, or approximately 1.18, or approximately 1.19, or approximately 1.20, or approximately 1.22, or approximately 1.23, or approximately 1.24, or approximately 1.25, or approximately 1.26, or approximately 1.27, or approximately 1.28, or approximately 1.29, or approximately 1.30, or approximately 1.31, or approximately 1.32, or approximately 1.33, or approximately 1.34, or approximately 1.35, or approximately 1.37, or approximately 1.38, or approximately 1.39, or approximately 1.40, or approximately 1.41, or approximately 1.42, or approximately 1.43, or approximately 1.44, or approximately 1.45, or approximately 1.46, or approximately 1.47, or approximately 1.48, or approximately 1.49, or about 1.50, or about 1.52, or about 1.53, or about 1.54, or about 1.55, or about 1.56, or about 1.57, or about 1.59, or about 1.60, or about 1.61, or about 1.62, or about 1.63, or about 1.64, or about 1.65, or about 1.66, or about 1.67, or about 1.68, or about 1.69, or about 1.70, or about 1.71, or about 1.72, or about 1.73, or about 1.74, or about 1.75, or about 1.76, or about 1.77, or about 1.78, or about 1.79, or about 1.80, or about 1.82, or about 1.83.

[0093] In some embodiments, the semi-crystalline polyamide (C) / reinforcing fiber (F) ratio is not 0.54, 0.89, 0.91, 1.01, 1.21, 1.36, 1.51, 1.58 or 1.81.

[0094] Other additives

[0095] In some embodiments, the polymer composition may optionally contain one or more additives. In some embodiments, the additives include one or more of the following: catalysts, polymers other than polyamides, adhesion promoters, ions, compounds, preservatives (such as heat stabilizers and antioxidants), lubricants, flow enhancers, or other components known in the art. Additives may include at least one of the following: inorganic stabilizers, organic stabilizers, flame retardants, lubricants, dyes, pigments, nucleating agents, flake metals, impact modifiers, antistatic agents, conductive additives, release agents, fluorescent whitening agents, adhesion promoters, aging inhibitors, antioxidants, anti-ozone agents, light stabilizers, UV stabilizers, UV absorbers, UV blockers, inorganic heat stabilizers, organic heat stabilizers, processing aids, crystallization promoters, crystallization delayers, flow aids, and reinforcing agents (e.g., fibrous materials and particulate fillers or fibers). They may also include hygroscopic agents, such as milled polyamide 66. For example, the composition may contain 0.01% to 20% by weight of a hygroscopic agent. These components may be considered optional. In some cases, the disclosed composition may explicitly exclude one or more of the additives described above in this section, for example, via the claims language. This is contemplated herein. For example, the disclosed composition may exclude flame retardants and / or reinforcing agents (or any other of the aforementioned additives). This supports the explicit exclusion of one or more of these components in the claims language.

[0096] In some embodiments, the provided composition comprises one or more heat stabilizers. One or more heat stabilizers in the composition can be selected to improve performance, such as at higher operating temperatures, without significantly adversely affecting the strength or other thermal properties of the material. At least one heat stabilizer may comprise copper. In some embodiments, all heat stabilizers in the membrane comprise copper. Suitable copper stabilizers for use as components of the provided membrane include copper halides, such as chlorides, bromides, or iodides, or combinations thereof. Copper stabilizers may also include copper cyanide, copper oxide, copper sulfate, copper phosphate, copper acetate, copper propionate, copper benzoate, copper adipic acid, copper terephthalate, copper isophthalate, copper salicylate, copper nicotinate, copper stearate, or copper complex salts coordinated with chelating amines (such as ethylenediamine and ethylenediaminetetraacetic acid), or combinations thereof.

[0097] In some embodiments, the composition comprises 0.01% to 2% by weight, or 0.01% to 1% by weight, or 0.01% to 0.15% by weight of at least one stabilizer, such as a heat stabilizer. In some embodiments, the at least one stabilizer (such as a heat stabilizer) comprises copper. For example, the at least one stabilizer comprises potassium iodide and / or cuprous iodide. In some embodiments, the composition comprises 0.10% to 0.15% by weight of potassium iodide and / or 0.03% to 0.15% by weight of cuprous iodide. For example, the composition comprises 0.12% by weight of potassium iodide and / or 0.03% by weight of cuprous iodide. In one embodiment, the total amount of the at least one stabilizer is 0.15% by weight. In another embodiment, the at least one stabilizer comprises a total of 0.15% by weight of potassium iodide and cuprous iodide.

[0098] In some embodiments, the combined concentration of one or more heat stabilizers in the composition is in the range of 0.1 wt% to 2 wt%, for example, 0.1 wt% to 0.6 wt%, 0.13 wt% to 0.81 wt%, 0.18 wt% to 1.1 wt%, 0.25 wt% to 1.5 wt%, or 0.33 wt% to 2 wt%. At the upper limit, the heat stabilizer concentration may be less than 2 wt%, for example, less than 1.5 wt%, less than 1.1 wt%, less than 0.81 wt%, less than 0.6 wt%, less than 0.45 wt%, less than 0.33 wt%, less than 0.25 wt%, less than 0.18 wt%, or less than 0.13 wt%. At the lower limit, the heat stabilizer concentration may be greater than 0.1 wt%, for example, greater than 0.13 wt%, greater than 0.18 wt%, greater than 0.25 wt%, greater than 0.33 wt%, greater than 0.45 wt%, greater than 0.6 wt%, greater than 0.81 wt%, greater than 1.1 wt%, or greater than 1.5 wt%. Higher concentrations, such as greater than 2% by weight, and lower concentrations, such as less than 0.1% by weight, were also considered.

[0099] In some embodiments, the provided composition comprises one or more lubricants selected as processing aids. The type and relative amount of lubricant can be selected to improve the processing of the composition and contribute to the high strength of the material. In some embodiments, the lubricant comprises wax. In some embodiments, the lubricant consists of wax. In some embodiments, the wax comprises fatty acids. In some embodiments, the lubricant consists of fatty acids. In some embodiments, the wax comprises saturated fatty acids. In some embodiments, the lubricant consists of saturated fatty acids. In some embodiments, the wax comprises stearic acid, behenic acid, or salts or combinations thereof. In some embodiments, the lubricant consists of stearic acid, behenic acid, or salts or combinations thereof. Stearate lubricants may include, for example, zinc stearate, calcium stearate, aluminum distearate, zinc stearate, and / or calcium stearate.

[0100] In some embodiments, the composition further comprises 0.1% to 2% by weight of at least one lubricant. In one aspect, the amount of lubricant is 0.1% to 0.5% by weight, such as 0.3% by weight.

[0101] In some embodiments, the combined concentration of one or more lubricants in the composition is in the range of 0.1 wt% to 2 wt%, for example, 0.1 wt% to 0.6 wt%, 0.13 wt% to 0.81 wt%, 0.18 wt% to 1.1 wt%, 0.25 wt% to 1.5 wt%, or 0.33 wt% to 2 wt%. With respect to the upper limit, the lubricant concentration may be less than 2 wt%, for example, less than 1.5 wt%, less than 1.1 wt%, less than 0.81 wt%, less than 0.6 wt%, less than 0.45 wt%, less than 0.33 wt%, less than 0.25 wt%, less than 0.18 wt%, or less than 0.13 wt%. With respect to the lower limit, the lubricant concentration may be greater than 0.1 wt%, for example, greater than 0.13 wt%, greater than 0.18 wt%, greater than 0.25 wt%, greater than 0.33 wt%, greater than 0.45 wt%, greater than 0.6 wt%, greater than 0.81 wt%, greater than 1.1 wt%, or greater than 1.5 wt%. Higher concentrations, such as greater than 2% by weight, and lower concentrations, such as less than 0.1% by weight, were also considered.

[0102] In some embodiments, at least one lubricant comprises aluminum stearate or zinc stearate. Preferably, zinc stearate.

[0103] In some embodiments, the provided composition comprises one or more reinforcing agents, such as mineral reinforcing materials or fiber reinforcing materials or combinations thereof. The reinforcing agents can be selected to further enhance the strength properties of the composition without compromising the desired thermal properties. The material of the filler is not particularly limited and can be selected from polyamide fillers known in the art. As a non-limiting example, the filler may include glass fibers and / or carbon fibers, particulate fillers such as mineral fillers based on natural and / or synthetic layered silicates, talc, mica, silicates, quartz, titanium dioxide, wollastonite, kaolinite, amorphous silica, magnesium carbonate, magnesium hydroxide, chalk, lime, feldspar, barium sulfate, Kevlar, etc. ® Fibers, basalt fibers, solid or hollow glass spheres or frosted glass, permanent magnets or magnetizable metal compounds and / or alloys and / or combinations thereof, and combinations thereof.

[0104] In some embodiments, the composition further comprises 15% to 60% by weight of at least one mineral or fiber reinforcing material. In some embodiments, the at least one mineral or fiber reinforcing material comprises glass fiber. In one embodiment, the composition comprises 30% to 40% by weight of at least one mineral or fiber reinforcing material. In one embodiment, the composition comprises 35% by weight of at least one mineral or fiber reinforcing material.

[0105] In some embodiments, at least one reinforcing filler (F) is glass fiber comprising NEG-249H and / or NEG-251H (HR).

[0106] In some embodiments, the combined concentration of one or more reinforcing agents in the composition is in the range of 15 wt% to 60 wt%, for example, 15 wt% to 42 wt%, 19.5 wt% to 46.5 wt%, 24 wt% to 51 wt%, 28.5 wt% to 55.5 wt%, or 33 wt% to 60 wt%. At the upper limit, the reinforcing agent concentration may be less than 60 wt%, for example, less than 55.5 wt%, less than 51 wt%, less than 46.5 wt%, less than 42 wt%, less than 37.5 wt%, less than 33 wt%, less than 28.5 wt%, less than 24 wt%, or less than 19.5 wt%. At the lower limit, the reinforcing agent concentration may be greater than 15 wt%, for example, greater than 19.5 wt%, greater than 24 wt%, greater than 28.5 wt%, greater than 33 wt%, greater than 37.5 wt%, greater than 42 wt%, greater than 46.5 wt%, greater than 51 wt%, or greater than 55.5 wt%. Higher concentrations, such as greater than 60% by weight, and lower concentrations, such as less than 15% by weight, were also considered.

[0107] In other cases, the polyamide composition is a "pure" composition, for example, the polyamide composition contains very little filler or no filler. For example, the polyamide composition may contain less than 20% by weight, such as less than 17% by weight, less than 15% by weight, less than 10% by weight, or less than 5% by weight of filler. In terms of range, the polyamide composition may contain 0.01% by weight to 20% by weight, such as 0.1% by weight to 15% by weight, or 0.1% by weight to 5% by weight of filler. In such cases, the amounts of other components can be adjusted accordingly based on the above component ranges and limitations. It is anticipated that those skilled in the art will be able to adjust the concentrations of other components in the polyamide composition based on the inclusion or exclusion of glass filler.

[0108] In some embodiments, the compositions of the present invention contain milled polyamide 66. For example, 0.55% by weight of milled polyamide 66.

[0109] Performance characteristics

[0110] The advantages of the compositions disclosed herein are that they can simultaneously provide effective damping properties and strong mechanical properties at high operating temperatures, such as in the temperature range of 20°C–180°C or above 60°C or 72°C. For the reasons stated above, it is challenging for conventional polyamide compositions to simultaneously provide these different performance characteristics under such temperature conditions.

[0111] Because polyamides are hygroscopic and tend to absorb moisture, and the performance characteristics of polyamide compositions can vary based on the moisture content of the composition, performance characteristics can be described at a defined moisture content that reflects the operating conditions expected for a particular end use. For example, performance characteristics can be characterized with a moisture content of less than 0.2% by weight.

[0112] One measure of the damping performance of the provided composition is the viscoelastic loss factor (tan(δ)) at which it exhibits its peak value at temperature. Generally, the higher the temperature at which this maximum value is reached, the better the composition dampens and isolates vibrations and noise at higher temperatures. The viscoelastic loss factor can be measured using standard test methods, for example, conforming to ISO 6721-1 (2019) and ASTM D5023-15 (2015).

[0113] In some embodiments, when the provided composition has a content less than

[0114] When the moisture content is 0.2% by weight, the composition is suitable for use at temperatures between 20°C and 180°C.

[0115] The composition exhibits maximum tan(δ) at temperatures ranging from 40°C to 140°C, 50°C to 140°C, 50°C to 120°C, 60°C to 115°C, 72°C to 110°C, 73°C to 103°C, for example, 73°C to 91°C, 76°C to 94°C, 79°C to 97°C, 82°C to 100°C, or 85°C to 103°C. Preferably, the temperature is above 60°C. The composition may also exhibit maximum tan(δ) at temperatures ranging from 75°C to 95°C, for example, 75°C to 87°C, 77°C to 89°C, 79°C to 91°C, 81°C to 93°C, or 83°C to 95°C. In terms of the upper limit, the maximum tan(δ) can occur at temperatures below 140°C, such as below 130°C, below 120°C, below 115°C, below 110°C, below 105°C, below 103°C, below 100°C, below 97°C, below 95°C, below 93°C, below 91°C, below 89°C, below 87°C, below 85°C, below 83°C, below 81°C, below 79°C, below 77°C, or below 75°C. Regarding the lower limit, the maximum tan(δ) can occur at temperatures greater than 40℃, such as greater than 42℃, greater than 50℃, greater than 55℃, greater than 60℃, greater than 65℃, greater than 70℃, greater than 72℃, greater than 73℃, greater than 75℃, greater than 77℃, greater than 79℃, greater than 81℃, greater than 83℃, greater than 85℃, greater than 87℃, greater than 89℃, greater than 91℃, greater than 93℃, greater than 95℃, greater than 97℃, or greater than 100℃. Higher maximum tan(δ) temperatures, such as greater than 103℃, have also been considered.

[0116] In some embodiments, the maximum tan(δ) has a value greater than 0.05, ranging from 0.15 to 0.85 (0.19 to 0.83). In another embodiment, the maximum tan(δ) may have a value in the range of 0.60 to 0.75. In one aspect, the maximum tan(δ) may have a value of 0.60, or 0.65, or 0.70 or 0.75. In an exemplary embodiment, when the composition has a moisture content of less than 0.2% by weight.

[0117] In some embodiments, when the composition has a moisture content of less than 0.2% by weight, the composition has, for example, a moisture content of 0.01 to 0.275, such as 0.01 to 0.245, 0.03 to 0.245, 0.05 to 0.245, 0.057 to 0.245, 0.07 to

[0118] 0.245, 0.095 to 0.245, 0.095 to 0.185, 0.11 to 0.2, 0.125 to 0.215,

[0119] The maximum tan(δ) value is in the range of 0.14 to 0.23 or 0.155 to 0.245. The composition may have a maximum tan(δ) value in the range of 0.095 to 0.15, for example, 0.095 to 0.128, 0.1005 to 0.1335, 0.106 to 0.139, 0.1115 to 0.1445 or 0.117 to 0.15. Regarding the upper limit, the maximum tan(δ) value can be less than 0.275, for example, less than 0.265, less than 0.245, less than 0.23, less than 0.215, less than 0.2, less than 0.185, less than 0.17, less than 0.155, less than 0.15, less than 0.1445, less than 0.139, less than 0.1335, less than 0.128, less than 0.1225, less than 0.117, less than 0.1115, less than 0.106, or less than 0.1005. Regarding the lower bound, the maximum tan(δ) value can be greater than 0.01, for example, greater than 0.03, greater than 0.05, greater than 0.095, greater than 0.1005, greater than 0.106, greater than 0.1115, greater than 0.117, greater than 0.1225, greater than 0.128, greater than 0.1335, greater than 0.139, greater than 0.1445, greater than 0.15, greater than 0.155, greater than 0.17, greater than 0.185, greater than 0.2, greater than 0.215, or greater than 0.23. Higher maximum tan(δ) values, such as greater than 0.245, are also considered. The expected, even higher, maximum tan(δ) values ​​are, for example, greater than 0.300, 0.300 to 0.400, 0.350, greater than 0.400, 0.400 to 0.500, 0.450, greater than 0.500, 0.500 to 0.600, 0.550, greater than 0.600, 0.650, 0.600 to 0.700, greater than 0.700, 0.750, and 0.700 to 0.800.

[0120] The heat deflection temperature (HDT) of a polymeric material is the temperature at which the material begins to soften and deform when exposed to a fixed load. The heat deflection temperature can be measured using, for example, the standard test method ISO 75-2 / A (2013). In some embodiments, when the composition has a moisture content of less than 0.2% by weight, the composition has an HDT at 1.82 MPa in the range of 185°C to 255°C, for example, 185°C to 227°C, 192°C to 234°C, 199°C to 241°C, 206°C to 248°C, or 213°C to 255°C. At the upper limit, the HDT can be less than 255°C, for example, less than 248°C, less than 241°C, less than 234°C, less than 227°C, less than 220°C, less than 213°C, less than 206°C, less than 199°C, or less than 192°C. Regarding the lower limit, HDT can be greater than 185°C, for example, greater than 192°C, greater than 199°C, greater than 206°C, greater than 213°C, greater than 220°C, greater than 227°C, greater than 234°C, greater than 241°C, or greater than 248°C. Higher temperatures, such as greater than 255°C, and lower temperatures, such as less than 185°C, are also considered.

[0121] In some embodiments, when the composition has a moisture content of less than 0.2% by weight, (1) the heat distortion temperature (HDT) of the composition at 1.82 MPa and (2) the melting temperature (T0) of the composition are... m The difference between them is in the range of 1℃ to 100℃ (15℃ to 45℃).

[0122] Melting temperature of polymer materials (T) m Melting temperature is the temperature at which a material undergoes a phase transition from crystallinity to solidity. Melting temperature can be measured using, for example, the standard test method ISO 11357-3 (2018). In some embodiments, when the composition has a moisture content of less than 0.2% by weight, the composition has a melting temperature (T) within the range of 205°C to 285°C, for example, 205°C to 253°C, 213°C to 261°C, 221°C to 269°C, 229°C to 277°C, or 237°C to 285°C. m In terms of the upper limit, T m It can be less than 285℃, for example, less than 277℃, less than 269℃, less than 261℃, less than 253℃, less than 245℃, less than 237℃, less than 229℃, less than 221℃, or less than 213℃. Regarding the lower limit, T... m Temperatures can be greater than 205°C, for example, greater than 213°C, greater than 221°C, greater than 229°C, greater than 237°C, greater than 245°C, greater than 253°C, greater than 261°C, greater than 269°C, or greater than 277°C. Higher temperatures, such as greater than 285°C, and lower temperatures, such as less than 205°C, are also considered.

[0123] HDT and T polymer materials m The differences can indicate the effect of reinforcing agents or other additives on the thermal properties of the material, and also affect the processability of the material. When the composition has a moisture content of less than 0.2% by weight, the provided composition's HDT and T... m The difference between them can be, for example, from 1°C to 100°C, or, for example, from 5°C to 95°C, 5°C to 80°C, 5°C to 65°C, 10°C to 60°C, 15°C to 60°C, 15°C to 50°C, 15°C to 45°C, 15°C to 35°C, 15°C to 27°C, 17°C to 29°C, 19°C to 31°C, 21°C to 33°C, or 23°C to 35°C. The HDT and T of the composition... m The difference between them can be between 20°C and 30°C, for example, 20°C to 26°C, 21°C to 27°C, 22°C to 28°C, 23°C to 29°C, or 24°C to 30°C. Regarding the upper limit, HDT and T... m The difference between them can be less than 100℃, for example, less than 95℃, less than 90℃, less than 85℃, less than 80℃, less than 75℃, less than 70℃, less than 65℃, less than 55℃, less than 50℃, less than 45℃, less than 40℃, less than 35℃, less than 33℃, less than 31℃, less than 30℃, less than 29℃, less than 28℃, less than 27℃, less than 26℃, less than 25℃, less than 24℃, less than 23℃, less than 22℃, less than 21℃, less than 20℃, less than 19℃, or less than 17℃. Regarding the lower limit, HDT and T... m The difference between these values ​​can be greater than 1℃, 3℃, 5℃, 7℃, 10℃, 15℃, 17℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃, 30℃, 31℃, or 33℃. Smaller differences, such as less than 15℃, are also considered.

[0124] In some embodiments, the polymer composition exhibits a center point beam tan(δ) value in the range of 0.095 to 0.245. This center point beam tan(δ) value provides a good measure of the damping performance of the composition because it quantifies the tan(δ) value over a wide operating spectrum (e.g., 1 Hz to 4000 Hz). The center point beam tan(δ) value can be in the range of, for example, 0.095 to 0.185, 0.11 to 0.2, 0.125 to 0.215, 0.14 to 0.23, or 0.155 to 0.245. The center point beam tan(δ) value can be in the range of 0.095 to 0.15, for example, 0.095 to 0.128, 0.1005 to 0.1335, 0.106 to 0.139, 0.1115 to 0.1445, or 0.117 to 0.15. Regarding the upper limit, the tan(δ) value of the beam at the center point can be less than 0.245, for example, less than 0.23, less than 0.215, less than 0.2, less than 0.185, less than 0.17, less than 0.155, less than 0.15, less than 0.1445, less than 0.139, less than 0.1335, less than 0.128, less than 0.1225, less than 0.117, less than 0.1115, less than 0.106, or less than 0.1005. Regarding the lower limit, the tan(δ) value of the beam at the center point can be greater than 0.095, for example, greater than 0.1005, greater than 0.106, greater than 0.1115, greater than 0.117, greater than 0.1225, greater than 0.128, greater than 0.1335, greater than 0.139, greater than 0.1445, greater than 0.15, greater than 0.155, greater than 0.17, greater than 0.185, greater than 0.2, greater than 0.215, or greater than 0.23. Higher tan(δ) values ​​at the center point of the beam, such as greater than 0.245, are also considered.

[0125] High tensile strength in polymer compositions can be advantageous, for example, because products made from these compositions consequently exhibit resistance to failure caused by tensile forces. The compositions disclosed herein can be advantageously demonstrated to exhibit no reduction in tensile strength compared to conventional polymer compositions that have not been modified to enhance high-temperature damping properties. Tensile strength can be measured using, for example, standard test methods ASTM D882-18 (2018) or ISO 527-2 (2012).

[0126] In some embodiments, the provided composition has a tensile strength in the range of 150 MPa to 255 MPa, for example, 150 MPa to 213 MPa, 160.5 MPa to 223.5 MPa, 171 MPa to 234 MPa, 181.5 MPa to 244.5 MPa, or 192 MPa to 255 MPa. The tensile strength of the composition can be in the range of 185 MPa to 205 MPa, for example, 185 MPa to 197 MPa, 187 MPa to 199 MPa, 189 MPa to 201 MPa, 191 MPa to 203 MPa, or 193 MPa to 205 MPa. In terms of upper limits, the tensile strength can be less than 255 MPa, for example less than 244.5 MPa, less than 234 MPa, less than 223.5 MPa, less than 213 MPa, less than 205 MPa, less than 203 MPa, less than 201 MPa, less than 199 MPa, less than 197 MPa, less than 195 MPa, less than 193 MPa, less than 191 MPa, less than 189 MPa, less than 187 MPa, less than 185 MPa, less than 181.5 MPa, less than 171 MPa, or less than 160.5 MPa. Regarding the lower limit, the tensile strength can be greater than 150 MPa, for example, greater than 160.5 MPa, greater than 171 MPa, greater than 181.5 MPa, greater than 185 MPa, greater than 187 MPa, greater than 189 MPa, greater than 191 MPa, greater than 193 MPa, greater than 195 MPa, greater than 197 MPa, greater than 199 MPa, greater than 201 MPa, greater than 203 MPa, greater than 205 MPa, greater than 213 MPa, greater than 223.5 MPa, greater than 234 MPa, or greater than 244.5 MPa. Higher tensile strengths, such as greater than 255 MPa, and lower strengths, such as less than 150 MPa, are also considered.

[0127] The strength of a polymer composition can also be characterized by its elongation properties. High elongation of polymer materials can be advantageous because products made from these materials are typically subjected to tensile forces that can cause materials with low elongation to tear or break. The compositions disclosed herein advantageously demonstrate no reduction in elongation compared to conventional polymer compositions that have not been modified to enhance high-temperature damping properties. Elongation can be measured using, for example, standard test methods ASTM D638 or ISO 527.

[0128] In some embodiments, the provided composition has an elongation at break ranging from 1.5% to 5%, for example, 1.5% to 3.6%, 1.85% to 3.95%, 2.2% to 4.3%, 2.55% to 4.65%, or 2.9% to 5%. At the upper limit, the elongation can be less than 5%, for example, less than 4.65%, less than 4.3%, less than 3.95%, less than 3.6%, less than 3.25%, less than 2.9%, less than 2.55%, less than 2.2%, or less than 1.85%. At the lower limit, the elongation can be greater than 1.5%, for example, greater than 1.85%, greater than 2.2%, greater than 2.55%, greater than 2.9%, greater than 3.25%, greater than 3.6%, greater than 3.95%, greater than 4.3%, or greater than 4.65%. Larger elongations, such as greater than 5%, and smaller elongations, such as less than 1.5%, are also considered.

[0129] The tensile modulus of a polymer composition is a measure of its resistance to tensile forces. A low tensile modulus in a polymer composition can be beneficial because a lower modulus can increase the elasticity of products made from the composition and make these products more suitable for processing steps involving stretching or thermoforming. The compositions disclosed herein can be advantageously demonstrated to have no increase in tensile modulus compared to conventional polymer compositions that have not been modified to enhance high-temperature damping properties. Tensile modulus can be measured using, for example, standard test methods such as ASTM D638 or ISO 527.

[0130] In some embodiments, the provided composition has a tensile modulus in the range of 9.5 GPa to 20.5 GPa, for example, 9.5 GPa to 16.1 GPa, 10.6 GPa to 17.2 GPa, 11.7 GPa to 18.3 GPa, 12.8 GPa to 19.4 GPa, or 13.9 GPa to 20.5 GPa. At the upper limit, the tensile modulus may be less than 20.5 GPa, for example, less than 19.4 GPa, less than 18.3 GPa, less than 17.2 GPa, less than 16.1 GPa, less than 15 GPa, less than 13.9 GPa, less than 12.8 GPa, less than 11.7 GPa, or less than 10.6 GPa. Regarding the lower limit, the tensile modulus can be greater than 9.5 GPa, for example, greater than 10.6 GPa, greater than 11.7 GPa, greater than 12.8 GPa, greater than 13.9 GPa, greater than 15 GPa, greater than 16.1 GPa, greater than 17.2 GPa, greater than 18.3 GPa, or greater than 19.4 GPa. Higher tensile moduli, for example, greater than 20.5 GPa, and lower tensile moduli, for example, less than 9.5 GPa, are also considered.

[0131] The impact strength of a polymer composition is a measure of its resistance to damage caused by impact loads. The compositions disclosed herein can be advantageously demonstrated to exhibit no reduction in impact strength compared to conventional polymer compositions that have not been modified to enhance high-temperature damping properties. Impact strength can be measured using standard test method ISO 179 (2010) according to, for example, notched Charpy impact strength or unnotched Charpy impact strength.

[0132] In some embodiments, the provided composition has a concentration of 7 kJ / m³. 2 Up to 15kJ / m 2 For example, 7kJ / m 2 Up to 11.8 kJ / m 2 7.8kJ / m 2 Up to 12.6 kJ / m 2 8.6kJ / m 2 Up to 13.4 kJ / m 2 9.4 kJ / m 2 Up to 14.2 kJ / m 2 or 10.2 kJ / m 2 Up to 15kJ / m 2 The notched Charpy impact strength within the specified range. At the upper limit, the notched Charpy impact strength can be less than 15 kJ / m. 2 For example, less than 14.2 kJ / m 2 Less than 13.4 kJ / m 2 Less than 12.6 kJ / m 2 Less than 11.8 kJ / m 2 Less than 11 kJ / m 2 Less than 10.2 kJ / m 2 Less than 9.4 kJ / m 2 Less than 8.6 kJ / m 2 or less than 7.8 kJ / m 2 Regarding the lower limit, the notched Charpy impact strength can be greater than 7 kJ / m. 2 For example, greater than 7.8 kJ / m 2 Greater than 8.6 kJ / m 2 Greater than 9.4 kJ / m 2 Greater than 10.2 kJ / m 2 Greater than 11 kJ / m 2 Greater than 11.8 kJ / m 2 Greater than 12.6 kJ / m 2 Greater than 13.4 kJ / m 2 or greater than 14.2 kJ / m 2 Higher strengths, such as greater than 15 kJ / m, were also considered. 2 And lower strength, such as less than 7 kJ / m2 .

[0133] In some embodiments, the provided composition has a concentration of 50 kJ / m³. 2 Up to 100kJ / m 2 For example, 50kJ / m 2 Up to 80kJ / m 2 55kJ / m 2 Up to 85kJ / m 2 60kJ / m 2 Up to 90kJ / m 2 65kJ / m 2 Up to 95kJ / m 2 or 70kJ / m 2 Up to 100kJ / m 2 The range of unnotched Charpy impact strength. At the upper limit, the unnotched Charpy impact strength can be less than 100 kJ / m. 2 For example, less than 95 kJ / m 2 Less than 90kJ / m 2 Less than 85kJ / m 2 Less than 80kJ / m 2 Less than 75kJ / m 2 Less than 70kJ / m 2 Less than 65kJ / m 2 Less than 60kJ / m 2 or less than 55kJ / m 2 Regarding the lower limit, the unnotched Charpy impact strength can be greater than 50 kJ / m. 2 For example, greater than 55 kJ / m 2 Greater than 60kJ / m 2 Greater than 65kJ / m 2 Greater than 70kJ / m 2 Greater than 75kJ / m 2 Greater than 80kJ / m 2 Greater than 85kJ / m 2 Greater than 90kJ / m 2 or greater than 95kJ / m 2 Higher strengths, such as greater than 100 kJ / m, were also considered. 2 and lower strength, such as less than 50 kJ / m 2 .

[0134] The strength of polymer compositions can also be characterized by their fatigue properties, such as tensile fatigue or bearing fatigue. High fatigue resistance in polymer materials can be beneficial because products made from these materials are typically subjected to loads that could cause cracking in materials with low fatigue resistance. The compositions disclosed herein advantageously demonstrate no reduction in fatigue resistance compared to conventional polymer compositions that have not been modified to enhance high-temperature damping properties.

[0135] In some embodiments, the composition comprises: 0% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 60% by weight of semi-crystalline PA6 polyamide; 0% to 20% by weight of semi-crystalline PA66 / 6 polyamide; 0% to 35% by weight of semi-crystalline PA9T polyamide; 15% to 50% by weight of amorphous polyamide; 30% to 40% by weight of glass fiber; 0.1% to 2% by weight of zinc stearate; and 0.03% to 0.15% by weight of a copper stabilizer, such as iodide. The composition contains: cuprous oxide; 0.10% to 0.15% by weight of a potassium stabilizer, such as potassium iodide; 1% to 5% by weight or 0% to 2% by weight of a colorant, such as black pigment concentrate, aniline black concentrate, or carbon black; and optionally less than 0.2% by weight of moisture; wherein the maximum tan(δ) value of the composition is greater than 0.05 and in the range of 0.15 to 0.85, and occurs in the temperature range of 20°C to 180°C, above 60°C, i.e., 60°C to 130°C, as measured according to the standard test method DMA. In one exemplary embodiment, the maximum tan(δ) value of the composition is in the range of 0.60 to 0.75. For example, the temperature range is 20°C to 180°C, above 60°C, 65°C to 130°C, e.g., 65.4°C to 113.9°C, including 86.9°C to 95.7°C.

[0136] In some embodiments, the composition has a tensile modulus in the range of 8780 MPa to 17000 MPa, as measured according to standard test method ISO 527. In some embodiments, the composition has a fracture stress in the range of 140 MPa to 240 MPa, as measured according to standard test method ISO 527. In some embodiments, the composition has a fracture strain in the range of 1.5% to 5.5%, as measured according to standard test method ISO 527. In some embodiments, the composition is readily moldable / processable, as measured according to industry standards.

[0137] In some embodiments, the composition has an elongation at break ranging from 1.5% to 5% as measured according to standard test methods ISO 527 or ASTM D638. In some embodiments, the composition has a tensile modulus ranging from 9.5 GPa to 20.5 GPa as measured according to standard test methods ISO 527 or ASTM D638. In some embodiments, the composition has a tensile modulus of 7 kJ / m². 2 Up to 15kJ / m 2 The notched Charpy impact strength is within the specified range. In some embodiments, the composition has a notched Charpy impact strength of 50 kJ / m. 2 Up to 100kJ / m 2 Unnotched Charpy impact strength within the range.

[0138] In some embodiments, the composition has a T value in the range of 205°C to 285°C. m In some embodiments, the composition has an HDT in the range of 185°C to 255°C at 1.82 MPa.

[0139] In some embodiments, the composition comprises: 0% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 55% by weight of semi-crystalline PA66 / 6I polyamide; 0% to 60% by weight of semi-crystalline PA6 polyamide; 0% to 20% by weight of semi-crystalline PA66 / 6 polyamide; 0% to 35% by weight of semi-crystalline PA9T polyamide; 15% to 50% by weight of amorphous polyamide; 30% to 40% by weight of glass fiber; and 0.1% to 2% by weight of zinc stearate. ; 0.03% to 0.15% by weight of a copper stabilizer, such as cuprous iodide; 0.10% to 0.15% by weight of a potassium stabilizer, such as potassium iodide; 0 to 2% by weight of a colorant, such as black pigment concentrate; and less than 0.2% by weight of moisture content; wherein the maximum tan(δ) of the composition occurs in the temperature range of 20°C to 180°C, i.e., above 60°C or in the range of 60°C to 130°C; and wherein the HDT of the composition (1) at 1.82 MPa and the T of the composition (2) are... m The difference between them is in the range of 15℃ to 45℃.

[0140] In some embodiments, the composition comprises: 0% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 55% by weight of semi-crystalline PA66 / 6I polyamide; 0% to 60% by weight of semi-crystalline PA6 polyamide; 0% to 20% by weight of semi-crystalline PA66 / 6 polyamide; 0% to 35% by weight of semi-crystalline PA9T polyamide; 15% to 50% by weight of amorphous polyamide; 30% to 40% by weight of glass fiber; 0. The composition comprises 1% to 2% zinc stearate; 0.03% to 0.15% copper stabilizer, such as cuprous iodide; 0.10% to 0.15% potassium stabilizer, such as potassium iodide; 0% to 2% colorant, such as black pigment concentrate; and less than 0.2% moisture content; wherein the maximum tan(δ) of the composition occurs in the temperature range of 20°C to 180°C, i.e., in the range of 60°C to 130°C; and wherein the tensile modulus measured according to standard test method ISO 527 is in the range of 8780 MPa to 17000 MPa. In some cases, the tensile modulus is greater than 8800 MPa or greater than 9500 MPa, and optionally, when the composition has less than 0.2% moisture content, the composition has a maximum viscoelastic loss factor (tan(δ)) in the temperature range of 20°C to 180°C or greater than 60°C or greater than 65°C.

[0141] In some cases, the tensile modulus is greater than 9.5 GPa, or greater than 10 GPa, or greater than 10.5 GPa, or greater than 11 GPa, or greater than 11.5 GPa, and optionally the geothermal deformation temperature is greater than 185°C.

[0142] In some embodiments, the composition comprises: 0% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 55% by weight of semi-crystalline PA66 / 6I polyamide; 0% to 70% by weight of a blend of polyamide and MPMD-T / MPMD-I; 0% to 60% by weight of semi-crystalline PA6 polyamide; 0% to 20% by weight of semi-crystalline PA66 / 6 polyamide; 0% to 35% by weight of semi-crystalline PA9T polyamide; and 15% to 50% by weight of amorphous polyamide. ; 30% to 40% by weight of glass fiber; 0.1% to 2% by weight of zinc stearate; 0.03% to 0.15% by weight of copper stabilizer, such as cuprous iodide; 0.10% to 0.15% by weight of potassium stabilizer, such as potassium iodide; 0% to 2% by weight of colorant, such as black pigment concentrate; and less than 0.2% by weight of moisture content; wherein the maximum tan(δ) of the composition occurs in the temperature range of 20°C to 180°C, i.e. above 60°C, in the range of 60°C to 130°C.

[0143] In some cases, the compositions of the present invention contain T g High T for 100℃ to 200℃ g Polymers and T g Low T from 0℃ to 160℃ g polymer.

[0144] In another embodiment, this disclosure relates to a composition comprising 0% to 55% by weight of a semi-crystalline PA66 / 6 (co)polyamide and 0% to 55% by weight of a second semi-crystalline polyamide or amorphous resin. Optionally, when the composition has a moisture content of less than 0.2% by weight, the composition has a maximum tan(δ) in the range of 20°C to 180°C, i.e., at a temperature greater than 60°C (range 65.4°C to 114.0°C). In some embodiments, the semi-crystalline PA66 / 6I polyamide has an isophthalic acid content in the range of 5 mol% to 30 mol%. In some embodiments, optionally, when the composition has a moisture content of less than 0.2% by weight, the maximum tan(δ) has a value in the range of 0.15 to 0.85 (0.60 to 0.75). In some embodiments, the amorphous polyamide has a glass transition temperature (Tg) greater than 100°C (range 100°C to 150°C). gIn some embodiments, the amorphous polyamide comprises a partially aromatic polyamide. In some embodiments, the amorphous polyamide comprises an amorphous copolyamide. In some embodiments, the second semi-crystalline polyamide comprises PA66 polyamide. In some embodiments, the second semi-crystalline polyamide comprises PA6 polyamide. In some embodiments, the second semi-crystalline polyamide comprises PA66 / I polyamide. In some embodiments, the second semi-crystalline polyamide comprises PA66 / 6 polyamide. In some embodiments, the second semi-crystalline polyamide comprises PA9T polyamide. In some embodiments, the composition further comprises 0.1% to 2% by weight of at least one lubricant. In one aspect, the amount of lubricant is 0.1% to 0.5% by weight, such as 0.3% by weight. In some embodiments, the lubricant comprises aluminum stearate or zinc stearate. In some embodiments, the composition further comprises 0.01% to 2% by weight of at least one heat stabilizer. In some embodiments, the heat stabilizer comprises copper and / or potassium. In some embodiments, the composition further comprises 15% to 60% by weight, for example 30% to 40% by weight, such as 35% by weight, at least one mineral or fiber reinforcement. In some embodiments, the mineral or fiber reinforcement includes glass fiber. In some embodiments, the composition has a tensile modulus in the range of 8780 MPa to 17000 MPa as measured according to standard test method ISO 527. In some embodiments, the composition has a fracture stress in the range of 140 MPa to 240 MPa as measured according to standard test method ISO 527. In some embodiments, the composition has a fracture strain in the range of 1.5% to 5.5% as measured according to standard test method ISO 527. In some embodiments, the composition is readily moldable / processable, as measured according to industry standards.

[0145] In some embodiments, the polyamide composition may have a tensile modulus greater than 8.7 GPa, a maximum viscoelastic loss factor (tanδ) of 0.09 or higher in the temperature range of 20°C to 180°C, i.e., greater than 60°C, and / or wherein the fracture stress is measured to be greater than 0.14 GPa at a fracture strain of greater than 2.4%.

[0146] In other embodiments, the maximum viscoelastic loss factor (tanδ) can have a value of 0.05 to 0.80 in the temperature range of 20°C to 180°C or at a temperature of 40°C to 180°C, preferably above 60°C.

[0147] In some embodiments, the polyamide composition exhibits a bimodal maximum viscoelastic loss factor (tanδ).

[0148] Applications (connecting parts / automotive parts)

[0149] This disclosure also relates to articles and (connecting) parts made from the disclosed polymer compositions. The properties of the polyamide compositions provide unexpected improvements in the performance of the articles / parts. In some cases, the part is a connecting part, and it can be used to connect one (automotive) component to another (automotive) component. For example, a connecting part can mount an engine to a chassis. The ability of the articles / parts (made from the disclosed NVH compositions) to effectively isolate vibrations (between the first and second components) results in quiet performance. Furthermore, the unexpected additional benefits in mechanical properties can facilitate the replacement of heavier structural components, which contributes to a much-desired weight reduction.

[0150] Furthermore, conventional connecting parts typically use conventional NVH-reducing components, such as rubber parts, often in conjunction with multiple rigid structural (metal) parts to achieve suitable connection and NVH performance. When the disclosed NVH composition is used for connecting parts, this multi-piece construction can be avoided, eliminating the need for multiple parts and improving manufacturing efficiency.

[0151] It has been found that the disclosed connecting parts are particularly effective in the automotive field. This is at least in part due to the ability of the compositions used to prepare them to provide NVH and mechanical properties, as discussed above.

[0152] In some embodiments, this disclosure relates to an (automotive) part that can be made from the disclosed polyamide composition. Due to the aforementioned performance characteristics of the polyamide composition, the resulting part exhibits improved NVH performance in balance with mechanical properties.

[0153] In some cases, the connecting part includes a part body (for contacting a first component) and a part tab (for connecting a second component). In use, the body is used to attach the component to one part of a vehicle, while the tab mounts the component to another part of the vehicle. For example, the part may be an engine mount, and the part body is disposed between the engine block and the chassis. The part body may be mounted to the engine block, and the tab may be mounted to the chassis. At least one of the part body and the part tab comprises (or is made of) the disclosed polyamide composition.

[0154] Numerous other parts have been considered. In most cases, parts are used to connect one component to another while providing unexpected improvements in the aforementioned NVH and mechanical performance. For example, parts can be engine mounts (e.g., for fuel or electric motors), differential mounts, torque bars, bushings, HVAC compressor brackets, strut mounts, shock absorber mounts, chassis mounts, accessory mounts (e.g., water pump mounts or compressor mounts), or transmission mounts, or combinations thereof. In some cases, parts may simply be inserts that can be added for NVH reduction. In some embodiments, the article can be molded from a blend of the polyamide compositions disclosed herein. On one hand, the article can be formed from the group selected from: engine mount brackets, differential mounts, torque bars, HVAC compressor brackets, strut mounts, shock absorber mounts, and transmission mounts. On the other hand, the engine mount bracket has a diameter greater than 30 mm. The engine mount bracket may contain two parts connected to each other. The two parts may have a total length greater than 80 mm. On one hand, the article may include fastening devices and / or mounting devices, and / or damping media.

[0155] Although not strictly necessary, connecting parts may also include structural supports. Structural supports are well known in the art. Specific examples include metal supports, such as aluminum or steel inserts.

[0156] This disclosure also relates to a method of connecting a first component to a second component using a connecting part. The method may include the step of providing a connecting part comprising a component body and component tabs. The method further includes the steps of contacting the component body with the first component and contacting the component tabs with the second component to connect the first and second components. The component exhibits the aforementioned performance benefits, which minimize NVH (noise, vibration, and harshness) issues. In a particular, non-limiting case, the connecting part is an engine mount, the first component is an engine, and the second component is a chassis.

[0157] In some embodiments, this disclosure relates to articles molded from resins having any of the compositions disclosed herein. The article may be a connecting part, which may include: a part body for contacting a first component; a part tab for contacting a second component to connect the first and second components; optional structural supports; at least one of the part body and the part tab may contain the aforementioned compositions. In some cases, the part is an engine mount, a differential mount, a torque lever and HVAC compressor bracket, a strut mount, a shock absorber mount, or a transmission mount, or a combination thereof.

[0158] In some embodiments, the present invention relates to a method for connecting a first component to a second component, the method comprising: providing a connecting part comprising a component body and a component tab; contacting the component body with the first component; and contacting the component tab with the second component to connect the first component and the second component, wherein optionally, when the composition has a moisture content of less than 0.2% by weight, the component has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C, i.e., greater than 60°C. The connecting part may be an engine mount, the first component may be an engine, and the second component may be a chassis.

[0159] method

[0160] Experimental samples were prepared for NVH (noise, vibration, and harshness) testing of engine mount components. Samples were compounded on a 25mm twin-screw extruder. The samples were then molded and tested for commercial grades. Commercial grades also contained blends of amorphous PA with PA66 and PA66 / 6.

[0161] Table 1 lists the formulations of Comparative Examples 1-6, including commercial grades.

[0162] Table 1. Comparison of polyamide compositions 1 to 6 .

[0163]

[0164] In some embodiments, a method for preparing a polyamide composition is disclosed. The method includes providing one or more semi-crystalline polyamides. The semi-crystalline polyamide can be any of those disclosed herein. In some embodiments, the method further includes providing one or more amorphous polyamides and / or PA66 / 6I copolyamides. The amorphous polyamide, semi-crystalline polyamide, or PA66 / 6I copolyamide can be any of those disclosed herein. In some embodiments, the method further includes providing one or more heat stabilizers, lubricants, and / or reinforcing agents. In some embodiments, the method further includes selecting the type of semi-crystalline polyamide, amorphous polyamide, PA66 / 6I copolyamide, heat stabilizer, lubricant, and / or reinforcing agent to provide the resulting polyamide composition with desired thermal, damping, and mechanical properties.

[0165] The method further includes blending one or more semi-crystalline polyamides (e.g., PA6, PA66, PA6 / 66, PA66 / 6I, PA66 / 6, PA66 / 6C, and PA9T) with amorphous polyamides (e.g., PA Amorph (Selar PA 3426) and blends thereof) or PA66 / 6I copolyamides. In some embodiments, the method further includes blending one or more heat stabilizers, lubricants, and / or reinforcing agents into the polyamide composition. In some embodiments, the method further includes selecting the amounts of semi-crystalline polyamides, amorphous polyamides, PA66 / 6I copolyamides, heat stabilizers, lubricants, and / or reinforcing agents to provide the resulting polyamide composition with desired thermal, damping, and mechanical properties. As used herein, the term "blending" is intended to cover adding the material itself to the composition or forming the material in situ within the composition. In some embodiments, two or more materials to be combined with the composition are added simultaneously via a masterbatch.

[0166] Example

[0167] This disclosure will be better understood in light of the following non-limiting embodiments. The following embodiments are intended for illustrative purposes only and are not intended to be construed in any way as limiting.

[0168] This limits the scope of this disclosure.

[0169] The polyamide compositions of Examples 1-12 of the present invention were prepared using the materials and amounts shown in Tables 2 and 3. Tensile modulus, fracture stress, fracture strain, peak value of tan(δ), peak value of tan(δ) (loss factor), and ease of molding / processability (i.e., "yes / no" indicating compliance with / below industry standards) were determined and recorded according to the standard procedures cited herein (i.e., ISO 527 and DMA).

[0170] Table 2. Polyamide compositions of Examples 1-6 of the present invention and their properties .

[0171]

[0172] Table 2 compares the properties of compositions 1-6 of the present invention. According to DMA results, the peak loss factor of several embodiments of the present invention is higher than 0.15, while the peak loss factor of the standard PA6 and PA66 grades is lower than 0.15.

[0173] Table 3. Polyamide compositions of Examples 7-12 of the present invention and their properties .

[0174]

[0175] Figures 1-3 The relevant DMA tan Delta curves for the data shown in Tables 1-3 are illustrated. The peak loss factor for all embodiments of the invention is 0.19 or higher. Figure 3 The relevant DMA tan Delta curve is shown. Figure 3 All embodiments of the invention shown have a high loss factor peak value greater than 0.4. Comparative Example 6 is difficult to mold and requires a long cycle time.

[0176] In general, polyamide compositions exhibiting high loss factor peaks in the temperature range of 20°C to 180°C have been discovered, wherein the compositions have an A / C ratio of 0.40 to 4.00. The maximum viscoelastic loss factor (tan(δ)) above 0.05 in the temperature range of 20°C–180°C of the compositions of the present invention can be achieved by adjusting the A / C ratio. Those skilled in the art, after reading the applicant's specification, can practice the claimed invention without excessive experimentation.

[0177] The polyamide compositions exhibit a high loss factor peak of over 0.05 in a temperature range of 20°C to 180°C, which can be used in damping applications such as vibration damping and noise suppression in automobiles. In one embodiment, these compositions are readily moldable / processable.

[0178] One of the key advantages of the polyamide compositions disclosed herein is their low hygroscopicity and mechanical properties that are less affected by DMA and conditioning conditions.

[0179] Implementation Plan

[0180] The following implementation schemes were considered. All combinations of features and implementation schemes were considered.

[0181] Embodiment 1: A composition comprising: one or more amorphous polyamides; and one or more semi-crystalline polyamides; wherein the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C; wherein the A / C ratio is from 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02. In one aspect, optionally when the composition has a moisture content of less than 0.2% by weight, the maximum viscoelastic loss factor (tan(δ)) is at a temperature greater than 40°C (ranging from 65°C to 130°C).

[0182] Implementation Scheme 2: According to the implementation scheme of Implementation Scheme 1, wherein the combined concentration of the one or more amorphous polyamides in the composition is in the range of 10% by weight to 90% by weight (e.g., 32% by weight to 38% by weight).

[0183] Implementation Scheme 3: According to the implementation scheme of Implementation Scheme 1 or 2, the combined concentration of the one or more semi-crystalline polyamides in the composition is in the range of 5% by weight to 80% by weight (e.g., 10% by weight to 80% by weight, or 26% by weight to 32% by weight).

[0184] Implementation Scheme 4: An implementation scheme according to any one of the implementation schemes of Implementation Scheme 1 to 3, wherein the A / C ratio is 0.55 to 0.99.

[0185] Implementation Scheme 5: An implementation scheme according to any one of the implementation schemes of Implementation Scheme 1 to 4, wherein the A / C ratio is 1.05 to 4.00.

[0186] Implementation Scheme 6: An implementation scheme according to any one of the implementation schemes of Implementation Scheme 1 to 5, wherein the semi-crystalline polyamide comprises at least one selected from the group consisting of PA66 / 6C, PA66, PA6 and PA66 / 6.

[0187] Implementation Scheme 7: An implementation scheme according to any one of the implementation schemes of Implementation Scheme 1 to 6, wherein the maximum tan(δ) has a value in the range of 0.15 to 0.85.

[0188] Implementation Scheme 8: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 1 to 7, wherein the composition has a tensile modulus greater than 8.7 GPa, and / or the maximum viscoelastic loss factor (tanδ) is 0.09 or higher, and / or the fracture stress is measured to be greater than 0.14 GPa at a fracture strain greater than 2.4%.

[0189] Implementation Scheme 9: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 1 to 8, wherein the composition has a tensile modulus greater than 8.8 GPa and / or a heat distortion temperature greater than 185°C.

[0190] Implementation Scheme 10: An implementation scheme according to any one of the implementation schemes of Implementation Scheme 1 to 9, wherein the amorphous polyamide comprises a polyamide blend of MPMD-T and MPMD-1.

[0191] Implementation Scheme 11: According to any one of the embodiments of embodiments 1 to 10, wherein the composition comprises: 0 wt% to 55 wt% of semi-crystalline PA66 polyamide; 0 wt% to 60 wt% of semi-crystalline PA6 polyamide; 0 wt% to 20 wt% of semi-crystalline PA66 / 6 polyamide; 0 wt% to 35 wt% of semi-crystalline PA9T polyamide; 15 wt% to 50 wt% of amorphous polyamide; 15 wt% to 60 wt% of glass fiber; 0.1 wt% to 2 wt% of stearate; 0.01 wt% to 2 wt% of stabilizer; and 0 wt% to 2 wt% of colorant.

[0192] Implementation Scheme 12: According to any one of the implementation schemes of Implementation Scheme 1 to 11, the implementation scheme comprises: 0.01% by weight to 2% by weight of heat stabilizer.

[0193] Embodiment 13: An embodiment of a composition comprising: >0 wt% to 50 wt% of a semi-crystalline PA66 / 6 (co)polyamide; 0 wt% to 55 wt% of a material selected from a list of compositions of a second semi-crystalline polyamide and an amorphous polyamide; wherein the composition has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C; and wherein the A / C ratio is 0.40 to 4.00, and excludes the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02;

[0194] Implementation Scheme 14: An embodiment of a composition comprising T g High T for 100℃ to 200℃ g Polymers and T g Low T from 0℃ to 160℃ g The polymer, wherein the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C, and wherein the A / C ratio is from 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

[0195] Embodiment 15: An embodiment of a connecting part, the part comprising: a part body for contacting a first component; and a part tab for contacting a second component to connect the first component and the second component, wherein at least one of the part body and the part tab comprises a composition comprising: one or more amorphous polyamides; and one or more semi-crystalline polyamides; and an A / C ratio of 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02; wherein optionally, when the composition has a moisture content of less than 0.2% by weight, the part has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C.

[0196] Embodiment 16: An embodiment of a connecting part, the part comprising: a part body for contacting a first component; and a part tab for contacting a second component to connect the first component and the second component, wherein at least one of the part body and the part tab comprises a composition comprising: 0 wt% to 55 wt% of semi-crystalline PA66 polyamide; 0 wt% to 60 wt% of semi-crystalline PA6 polyamide; 0 wt% to 20 wt% of semi-crystalline PA66 / 6 polyamide; 0 wt% to 35 wt% of semi-crystalline PA9T polyamide; 15 wt% to 50 wt% of amorphous polyamide; 15 wt% to 60 wt% of glass fiber; and 0.1 wt% to 2 wt% of stearate.

[0197] 0.01% to 2% by weight of stabilizer; 0% to 2% by weight of colorant; wherein the part has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C; wherein the A / C ratio is 0.40 to 4.00, and does not include the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

[0198] Implementation Scheme 17: According to the implementation scheme described in Implementation Scheme 15 or 16, the implementation scheme further includes structural support components.

[0199] Implementation Scheme 18: According to the implementation scheme of 15 or 16, wherein the part is an engine mount, a differential mount, a torque rod and HVAC compressor bracket, a strut mount, a shock absorber mount or a transmission mount or a combination thereof.

[0200] Implementation Scheme 19: An embodiment of a method for connecting a first component to a second component, the method comprising: providing a connecting component including a component body and a component tab; contacting the component body with the first component; and contacting the component tab with the second component to connect the first component and the second component, wherein the component has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C; wherein the A / C ratio is from 0.40 to 4.00, and excludes the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

[0201] Implementation Scheme 20: According to the implementation scheme of Implementation Scheme 19, wherein the connecting part is an engine mounting part, the first component is an engine, and the second component is a chassis.

[0202] Implementation Scheme 21: According to the implementation scheme described in Implementation Scheme 1, the implementation scheme comprises: 0 wt% to 55 wt% of semi-crystalline PA66 polyamide; 0 wt% to 55 wt% of semi-crystalline PA66 / 6I polyamide; 0 wt% to 55 wt% of semi-crystalline PA6 polyamide; 0 wt% to 55 wt% of semi-crystalline PA66 / 6 polyamide; 0 wt% to 55 wt% of semi-crystalline PA9T polyamide; 10 wt% to 90 wt% of amorphous polyamide; and 15 wt% to 60 wt% of glass. Fiber; 0.1% to 2% aluminum stearate; 0.1% to 2% copper heat stabilizer; 0% to 6% colorant; and less than 0.2% moisture content; wherein the maximum tan(δ) of the composition occurs in the temperature range of 20°C to 180°C, such as above 60°C or 75°C to 95°C; and wherein the difference between (1) the HDT of the composition at 1.82 MPa and (2) the Tm of the composition is in the range of 15°C to 45°C.

[0203] Embodiment 22: An embodiment of any of the compositions of the present invention, wherein the embodiment has a tensile strength in the range of 150 MPa to 255 MPa as measured according to standard test methods ASTM D638 or ISO 527.

[0204] Implementation Scheme 23: According to the implementation scheme of Implementation Scheme 1, the implementation scheme comprises: 20% to 55% by weight of semi-crystalline PA66 polyamide; 20% to 55% by weight of semi-crystalline PA66 / 61 polyamide; 0% to 11% by weight of semi-crystalline PA6 polyamide; 8% to 40% by weight of amorphous polyamide; 15% to 60% by weight of glass fiber; 0.1% to 2% by weight of aluminum stearate; 0.1% to 2% by weight of copper heat stabilizer; 0% to 6% by weight of colorant; and less than 0.2% by weight of moisture content; wherein the maximum tan(δ) of the composition occurs in the temperature range of 20°C to 180°C, above 60°C, or 75°C to 95°C; and wherein the tensile strength of the composition is in the range of 185 MPa to 205 MPa.

[0205] Embodiment 24: An embodiment of the composition of the present invention having an elongation at break in the range of 1.5% to 5% as measured according to standard test methods ASTM D638 or ISO 527.

[0206] Embodiment 25: An embodiment of the composition of the present invention having a tensile modulus greater than 9.5 GPa, for example, in the range of 9.5 GPa to 20.5 GPa, as measured according to standard test methods ASTM D638 or ISO 527.

[0207] Embodiment 26: An embodiment of any of the compositions of the present invention, said embodiment having a notched Charpy impact strength in the range of 7 kJ / m² to 15 kJ / m².

[0208] Embodiment 27: An embodiment of any of the compositions of the present invention, said embodiment having an unnotched Charpy impact strength in the range of 50 kJ / m² to 100 kJ / m².

[0209] Embodiment 28: An embodiment of any of the compositions of the present invention, said embodiment having a T value in the range of 205°C to 285°C. m .

[0210] Embodiment 29: An embodiment of any of the compositions of the present invention, said embodiment having an HDT greater than 185°C at 1.82 MPa, for example in the range of 185°C to 255°C.

[0211] Implementation Scheme 30: A composition comprising: 1% to 50% by weight of a semi-crystalline PA66 / 6 (co)polyamide; 30% to 80% by weight of a material selected from a list of second semi-crystalline polyamides and amorphous polyamides; wherein when the composition has a moisture content of less than 0.2% by weight, the composition has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C, i.e., greater than 60°C (73°C to 103°C).

[0212] Implementation Scheme 31: According to the implementation scheme of Implementation Scheme 30, wherein the second semi-crystalline polyamide comprises PA66 / I polyamide having an isophthalic acid content in the range of 5 mol% to 30 mol%.

[0213] Implementation Scheme 32: According to the implementation scheme of Implementation Scheme 30 or 31, wherein when the composition has a moisture content of less than 0.2% by weight, the maximum tan(δ) has a value in the range of 0.057 to 0.245 (0.095 to 0.245).

[0214] Implementation Scheme 33: An embodiment according to any one of embodiments 30 to 32, wherein the amorphous polyamide has a glass transition temperature (T0) greater than 100°C (ranging from 100°C to 150°C). g ).

[0215] Implementation Scheme 34: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 33, wherein the amorphous polyamide comprises a portion of aromatic polyamide.

[0216] Implementation Scheme 35: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 34, wherein the amorphous polyamide comprises an amorphous copolyamide.

[0217] Implementation Scheme 36: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 35, wherein the second semi-crystalline polyamide comprises PA66 polyamide.

[0218] Implementation Scheme 37: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 36, wherein the second semi-crystalline polyamide comprises PA6 polyamide.

[0219] Implementation Scheme 38: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 37, wherein the second semi-crystalline polyamide comprises PA66 / I polyamide.

[0220] Implementation Scheme 39: According to any one of the implementation schemes of Implementation Schemes 30 to 38, the implementation scheme further comprises: 0.1% to 2% by weight of one or more lubricants.

[0221] Implementation Scheme 40: According to the implementation schemes of Implementation Schemes 30 to 39, wherein one or more lubricants comprise aluminum stearate.

[0222] Implementation Scheme 41: According to any one of the implementation schemes of Implementation Scheme 30 to 40, the implementation scheme further comprises: 0.1% to 2% by weight of one or more heat stabilizers.

[0223] Implementation Scheme 42: According to the implementation scheme of Implementation Scheme 41, at least one of the heat stabilizers includes copper.

[0224] Implementation Scheme 43: According to any one of the implementation schemes of Implementation Schemes 30 to 42, the implementation scheme further comprises: 15% to 60% by weight of one or more mineral or fiber reinforcing materials.

[0225] Implementation Scheme 44: According to the implementation scheme of Implementation Scheme 43, wherein the one or more mineral or fiber reinforcing materials include glass fibers.

[0226] Implementation Scheme 45: An implementation scheme according to any one of the implementation schemes of Implementation Scheme 30 to 44, wherein the implementation scheme has a tensile strength in the range of 150 MPa to 255 MPa as measured according to standard test methods ASTM D638 or ISO 527.

[0227] Implementation Scheme 46: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 45, wherein the implementation scheme has an elongation at break in the range of 1.5% to 5% as measured according to standard test methods ASTM D638 or ISO 527.

[0228] Implementation Scheme 47: An implementation scheme according to any one of the implementation schemes of Implementation Schemes 30 to 46, wherein the implementation scheme has a tensile modulus in the range of 9.5 GPa to 20.5 GPa as measured according to standard test methods ASTM D638 or ISO 527.

[0229] Implementation Scheme 48: An implementation scheme according to any one of the implementation schemes 30 to 47, wherein the implementation scheme has 7 kJ / m 2 Up to 15kJ / m 2 Charpy impact strength within the range of notches.

[0230] Implementation Scheme 49: An implementation scheme according to any one of the implementation schemes 30 to 48, wherein the implementation scheme has 50 kJ / m 2 Up to 100kJ / m 2 Unnotched Charpy impact strength within the range.

[0231] Implementation Scheme 50: An article of manufacture molded from a resin having a composition according to any one of the embodiments of embodiments 1 to 49.

[0232] Implementation Scheme 51: A composition comprising one or more amorphous polyamides; one or more semi-crystalline polyamides; wherein optionally, when the composition has a moisture content of less than 0.2% by weight, the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C or greater than 60°C.

[0233] Implementation Scheme 52: According to the implementation scheme of Implementation Scheme 51, wherein the combined concentration of the one or more amorphous polyamides in the composition is in the range of 10% by weight to 70% by weight.

[0234] Implementation Scheme 53: According to the implementation scheme of Implementation Scheme 51 or 52, wherein the combined concentration of the one or more semi-crystalline polyamides in the composition is in the range of 10% by weight to 70% by weight.

[0235] Implementation Scheme 54: According to any one of Implementation Schemes 51 to 53, wherein the semi-crystalline polyamide comprises PA66 / 6C.

[0236] Embodiment 55: An embodiment according to any one of embodiments 51 to 54, wherein the composition comprises 10% to 70% by weight of PA66 / 6C.

[0237] Implementation Scheme 56: An embodiment according to any one of Implementation Schemes 51 to 55, wherein the tensile modulus is greater than 9.5 GPa, and wherein, optionally when the composition has a moisture content of less than 0.2% by weight, the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C or greater than 60°C.

[0238] Implementation Scheme 57: According to any one of Implementation Schemes 51 to 56, wherein the tensile modulus is greater than 9.5 GPa and the heat distortion temperature is greater than 185°C.

[0239] Implementation Scheme 58: According to any one of Implementation Schemes 51 to 57, wherein the amorphous polyamide comprises a polyamide blend of MPMD-T and MPMD-1.

[0240] Implementation Scheme 59: According to any one of Implementation Schemes 51 to 58, wherein the amorphous polyamide comprises a polyamide blend of MPMD-T and MPMD-1, and the semi-crystalline polyamide comprises PA66 / 6C.

[0241] Embodiment 60: An embodiment according to any one of embodiments 51 to 59, wherein the embodiment comprises: 20% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 11% by weight of semi-crystalline PA6 polyamide; 10% to 70% by weight of a blend of polyamide and MPMD-T / MPMD-1; 15% to 60% by weight of glass fiber; 0.1% to 2% by weight of stearate; 0.1% to 2% by weight of heat stabilizer; 0% to 6% by weight of colorant; and optionally less than 0.2% by weight of moisture content.

[0242] Embodiment 61: According to any one of Embodiments 51 to 60, the embodiment comprises 10% to 70% by weight of semi-crystalline PA66 / 6C; 0% to 11% by weight of semi-crystalline PA6 polyamide; 10% to 70% by weight of amorphous polyamide; 15% to 60% by weight of glass fiber; 0.1% to 2% by weight of stearate; 0.1% to 2% by weight of heat stabilizer; 0% to 6% by weight of colorant; and less than 0.2% by weight of moisture content.

[0243] Implementation Scheme 62: A composition comprising: T g High T for 100℃ to 200℃ g The polymer and Tg are low Tg polymers ranging from 0°C to 160°C, wherein optionally when the composition has a moisture content of less than 0.2% by weight, the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C or greater than 60°C to 180°C.

[0244] Implementation Scheme 63: A connecting part comprising: a part body for contacting a first component; and a part tab for contacting a second component to connect the first component and the second component, wherein at least one of the part body and the part tab comprises a composition comprising: one or more amorphous polyamides; and one or more semi-crystalline polyamides; wherein optionally, when the composition has a moisture content of less than 0.2% by weight, the part has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C, i.e., greater than 60°C to 180°C.

[0245] Implementation Scheme 64: A connecting part comprising: a part body for contacting a first component, and a part tab for contacting a second component to connect the first component and the second component, wherein at least one of the part body and the part tab comprises a composition comprising: 1 wt% to 50 wt% of a semi-crystalline PA66 / 6 (co)polyamide; 30 wt% to 80 wt% of a material selected from a list of second semi-crystalline polyamides and amorphous polyamides; wherein optionally, when the composition has a moisture content of less than 0.2 wt%, the part has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C, i.e., greater than 60°C to 180°C.

[0246] Implementation Scheme 65: According to the implementation scheme of Implementation Scheme 63 or 64, the implementation scheme further includes structural support components.

[0247] Implementation Scheme 66: According to any one of Implementation Schemes 63 to 65, the part is an engine mount, a differential mount, a torque rod and HVAC compressor bracket, a strut mount, a shock absorber mount or a transmission mount or a combination thereof.

[0248] Implementation Scheme 67: A method for connecting a first component to a second component, the method comprising: providing a connecting component including a component body and a component tab; contacting the component body with the first component; and contacting the component tab with the second component to connect the first component and the second component, wherein optionally when the composition has a moisture content of less than 0.2% by weight, the component has a maximum tan(δ) greater than 0.05 at a temperature greater than 20°C to 180°C, preferably greater than 60°C.

[0249] Implementation Scheme 68: According to the implementation scheme of Implementation Scheme 67, the connecting part is an engine mounting part, the first component is an engine, and the second component is a chassis.

[0250] Implementation Scheme 69: Use of the polyamide composition of the present invention in the manufacture of articles for vibration damping and noise suppression.

[0251] Implementation Scheme 70: The polyamide composition of the present invention is used for damping at elevated temperatures and / or for vibration damping of transport vehicles.

[0252] Although the invention has been described in detail, modifications within the spirit and scope of the invention will be apparent to those skilled in the art from the foregoing discussion, relevant knowledge in the art, and the references discussed above in conjunction with the background and specific embodiments, all of which are incorporated herein by reference. Furthermore, it should be understood that various aspects of the invention, as well as parts of the various embodiments and the various features in the stated and / or appended claims, can be combined or interchanged in whole or in part. In the foregoing description of the various embodiments, as will be understood by those skilled in the art, those embodiments relating to another embodiment can be suitably combined with other embodiments. Moreover, those skilled in the art will understand that the foregoing description is merely illustrative and not intended to limit the invention.

Claims

1. A composition comprising: One or more amorphous polyamides (A); One or more semi-crystalline polyamides (C); The composition described herein has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C. The A / C ratio is between 0.40 and 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.

02.

2. The composition according to claim 1, wherein the combined concentration of the one or more amorphous polyamides in the composition is in the range of 10% by weight to 90% by weight.

3. The composition according to any of the preceding claims, wherein the combined concentration of the one or more semi-crystalline polyamides in the composition is in the range of 5% by weight to 80% by weight.

4. The composition according to any of the preceding claims, wherein the A / C ratio is from 0.55 to 0.

99.

5. The composition according to any of the preceding claims, wherein the A / C ratio is from 1.05 to 4.

00.

6. The composition according to any of the preceding claims, wherein the semi-crystalline polyamide comprises at least one selected from the group consisting of PA66 / 6C, PA66, PA6, and PA66 / 6.

7. The composition according to any of the preceding claims, wherein the maximum tan(δ) has a value in the range of 0.15 to 0.

85.

8. The composition according to any of the preceding claims, wherein the composition has a tensile modulus greater than 8.7 GPa, and / or the maximum viscoelastic loss factor (tan(δ)) is 0.09 or higher, and / or wherein the fracture stress is measured to be greater than 0.14 GPa at a fracture strain greater than 2.4%.

9. The composition according to any of the preceding claims, wherein the composition has a tensile modulus greater than 8.8 GPa and / or a heat distortion temperature greater than 185°C.

10. The composition according to any of the preceding claims, wherein the amorphous polyamide comprises a polyamide blend of MPMD-T and MPMD-1.

11. The composition according to any of the preceding claims, wherein the composition comprises: 0% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 60% by weight of semi-crystalline PA6 polyamide; 0% to 20% by weight of semi-crystalline PA66 / 6 polyamide; 0% to 35% by weight of semi-crystalline PA9T polyamide; 15% to 50% by weight of amorphous polyamide. 15% to 60% by weight of glass fiber; 0.1% to 2% by weight of stearates; Stabilizer of 0.01% to 2% by weight; 0% to 2% by weight of colorant.

12. The composition according to any preceding claim, wherein the composition comprises: 0.01% to 2% by weight of heat stabilizer.

13. A composition comprising: >0% to 50% by weight of semi-crystalline PA66 / 6 (co)polyamide; 0% to 55% by weight of materials selected from the list of second semi-crystalline polyamides and amorphous polyamides; The composition described above has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C; and The A / C ratio is between 0.40 and 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.

02.

14. A composition comprising: T g High T for 100℃ to 200℃ g Polymers and T g Low T from 0℃ to 160℃ g The polymer, wherein the composition has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in a temperature range of 20°C to 180°C, and wherein the A / C ratio is from 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

15. A connecting part, the part comprising: The main body of the part used to contact the first component; as well as A component tab for contacting a second component to connect the first component and the second component, wherein at least one of the component body and the component tab comprises a composition comprising: One or more amorphous polyamides; and One or more semi-crystalline polyamides; and the A / C ratio is from 0.40 to 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01 and 1.02; Optionally, when the composition has a moisture content of less than 0.2% by weight, the part has a maximum viscoelastic loss factor (tan(δ)) greater than 0.05 in the temperature range of 20°C to 180°C.

16. A connecting part, the part comprising: The main body of the part used to contact the first component; as well as A component tab for contacting a second component to connect the first component and the second component, wherein at least one of the component body and the component tab comprises a composition comprising: 0% to 55% by weight of semi-crystalline PA66 polyamide; 0% to 60% by weight of semi-crystalline PA6 polyamide; 0% to 20% by weight of semi-crystalline PA66 / 6 polyamide; 0% to 35% by weight of semi-crystalline PA9T polyamide; 15% to 50% by weight of amorphous polyamide; 15% to 60% by weight of glass fiber; 0.1% to 2% by weight of stearates; Stabilizer of 0.01% to 2% by weight; 0% to 2% by weight of colorant; The component described above has a maximum tan(δ) greater than 0.05 in the temperature range of 20℃ to 180℃; The A / C ratio is between 0.40 and 4.00, excluding the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02; Optionally, when the composition has a moisture content of less than 0.2% by weight.

17. The connecting part according to claim 15 or 16, wherein the connecting part further comprises a structural support member.

18. The connecting part according to claim 15 or 16, wherein the part is an engine mount, a differential mount, a torque rod and HVAC compressor bracket, a strut mount, a shock absorber mount, or a transmission mount, or a combination thereof.

19. A method for connecting a first component to a second component, the method comprising: Provide connecting parts including the part body and part connectors; Make the main body of the part contact the first component; The component tab contacts the second component to connect the first and second components, wherein the component has a maximum tan(δ) greater than 0.05 in a temperature range of 20°C to 180°C; wherein the A / C ratio is from 0.40 to 4.00, and excludes the following ratios: 0.50, 0.51, 0.79, 1.00, 1.01, and 1.02; optionally when the composition has a moisture content of less than 0.2% by weight.

20. The method of claim 19, wherein the connecting part is an engine mounting component, the first component is an engine, and the second component is a chassis.

Citation Information

Patent Citations

  • Vibration damping material of polyamides and mercaptobenzoimidazoles

    US20080026246A1

  • Polyamide formulations for improved noise vibration and harshness

    US20210355322A1

  • Noise damping compositions

    WO2012092093A1